Adhesive tape for dicing and method for producing semiconductor chip
By using an adhesive composition composed of silicone gel and resin, combined with a thermal polymerization initiator and a photosensitive platinum catalyst, the problems of insufficient adhesion during cutting of a semiconductor chip and residual glue during peeling are solved, and efficient chip cutting and good pick-upability are achieved.
Patent Information
- Application Number
- CN202080088643.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-11-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-11-09
AI Technical Summary
When cutting a semiconductor chip with a cutting adhesive tape, the composition of the adhesive layer and the raw material of the coating material lead to insufficient adhesion, causing the chip to scatter; in order to improve adhesion, the spherical adhesion and adhesion of the adhesive layer are designed to be high, resulting in the generation of residual glue during peeling.
Adhesive compositions composed of silicone gel material, silicone resin, crosslinking agent, thermal polymerization initiator and photosensitive platinum catalyst are used to adjust the mixing ratio of the silicone gel material and the content of alkenyl groups bonded to silicon atoms, combined with the effect of the thermal polymerization initiator, crosslinking and curing after heating and drying, and improving adhesion and adhesion force; during peeling, the photosensitive platinum catalyst is activated by ultraviolet irradiation to promote crosslinking reaction, reduce the adhesion force of the adhesive layer, and avoid the generation of residual glue.
Good adhesion and adhesion force when cutting the semiconductor chip is achieved, preventing the chip from scattering, and effectively reducing the adhesion force of the adhesive layer during peeling, avoiding the generation of residual glue, and ensuring good pick-upability of the semiconductor chip.
Smart Images

Figure CN114868229B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a dicing adhesive tape used for dicing a semiconductor material as a semiconductor chip material, and a method for manufacturing a semiconductor chip using the dicing adhesive tape. Background Art
[0002] Conventionally, as a dicing adhesive tape for producing a semiconductor chip having an LED (Light Emitting Diode) or the like, an adhesive tape having an adhesive layer composed of an acrylic resin is known (see Patent Document 1).
[0003] Furthermore, as a dicing adhesive tape for producing a semiconductor chip having an LED or the like, an adhesive tape having an adhesive layer composed of a silicone-based resin is known (see Patent Documents 2 and 3).
[0004] Furthermore, as a method for producing semiconductor chips using a dicing tape, there is known a method in which an adhesive tape is attached to the substrate side of a semiconductor element substrate having a plurality of semiconductor elements formed thereon, and the semiconductor element substrate is cut by a dicing machine (see Patent Document 4).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-38408
[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-050216
[0009] Patent Document 3: Japanese Patent Application Publication No. 2016-122812
[0010] Patent Document 4: Japanese Patent Application Publication No. 2005-93503 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In addition, in recent years, as a method for producing semiconductor chips that are singulated by dicing, the following technology has been proposed: a technology in which an adhesive tape is attached to a semiconductor material formed by coating a plurality of semiconductor elements with a coating material such as a sealing resin or a phosphor and then dicing the semiconductor material; a technology corresponding to the so-called wafer-level CSP (chip-scale packaging) process.
[0013] In this way, when the adhesive tape is attached to the semiconductor material formed by coating the semiconductor element with the coating material, the adhesive strength may be insufficient due to the composition of the adhesive layer in the adhesive tape, the raw material of the coating material, etc., and the semiconductor chips separated by dicing may fly away. In addition, if the ball viscosity and adhesive strength of the adhesive layer are designed to be high in order to suppress the scattering of the semiconductor chips, when the obtained semiconductor chips are peeled off from the adhesive tape, the so-called adhesive residue may be generated in which the adhesive remains in a state of being attached to the semiconductor chips.
[0014] The object of the present invention is to provide an adhesive tape for dicing which has good adhesion and tackiness to a semiconductor material having a plurality of semiconductor elements covered with a covering material and which suppresses residual adhesive on the semiconductor chip when the semiconductor chip singulated by dicing is peeled off, and a method for manufacturing a semiconductor chip using the same.
[0015] Methods for solving problems
[0016] Based on such a purpose, the present inventors have conducted in-depth research on the adhesive layer of an adhesive tape for dicing, and found that: if the adhesive layer is composed of an adhesive composition further adding (4) a photosensitive platinum (Pt) catalyst to a specific resin composition comprising at least (1) a silicone resin comprising an organic silicone material composed of an organic polysiloxane containing an alkenyl group bonded to a silicon atom, (2) a cross-linking agent having a hydrogen atom (SiH group) bonded to a silicon atom, and (3) a thermal polymerization initiator composed of a peroxide, and the mixing ratio of the organic silicone material to the silicone resin in the silicone resin and the content of the alkenyl group bonded to a silicon atom in the silicone resin as a whole are set to a predetermined range, then the semiconductor material having a plurality of semiconductor elements coated with a coating material has stable and good adhesion, and when the semiconductor chips singulated by dicing are peeled off, the residual adhesive on the semiconductor chips can be suppressed, thereby completing the present invention.
[0017] That is, it was found that: by forming the adhesive layer of the adhesive tape for dicing from an adhesive composition obtained by mixing an organic silicone material and an organic silicone resin in a predetermined ratio and having a predetermined amount of alkenyl groups bonded to silicon atoms, a crosslinking agent, a thermal polymerization initiator and a photosensitive platinum (Pt) catalyst are added, the following effects are achieved. First, it was found that: when a semiconductor material having a plurality of semiconductor elements coated with a coating material is divided into a plurality of semiconductor chips, when the adhesive layer undergoes a heating and drying process for forming the adhesive layer on a substrate, a portion of the organic silicone resin is crosslinked and cured (a first-stage crosslinking reaction) due to the thermal polymerization initiator, and therefore, the stable and good adhesive force and adhesion brought about by the moderate cohesive force of the adhesive layer can suppress the scattering of the singulated semiconductor chips during dicing. In addition, on the other hand, when the semiconductor chip singulated by cutting is peeled off from the dicing adhesive tape, the photosensitive platinum (Pt) catalyst in the adhesive composition can be activated by irradiating the adhesive layer with light such as ultraviolet rays, promoting the second-stage crosslinking reaction (addition reaction) between the alkenyl group bonded to the silicon atom of the organic silicone material in the silicone resin and the hydrogen atom (SiH group) bonded to the silicon atom of the crosslinking agent, and the crosslinking density becomes higher, so the cohesive force of the adhesive composition becomes larger than before light irradiation. As a result, the viscosity of the adhesive layer is appropriately reduced, and the failure mode in the further holding force test is "interface peeling" or "no falling" in the holding force test. It is found that the pickup of the semiconductor chip from the dicing adhesive tape becomes good, and the residual glue on the semiconductor chip can be suppressed.
[0018] The dicing adhesive tape of the present invention is a dicing adhesive tape characterized in that it is a dicing adhesive tape used when a semiconductor material having a plurality of semiconductor elements covered with a covering material is divided into a plurality of semiconductor chips and comprises a substrate and an adhesive layer laminated on the substrate, wherein the adhesive layer is composed of an adhesive composition, and the adhesive composition comprises: a silicone resin obtained by mixing an organic silicone material (G) and an organic silicone resin (R), and at least one molecule of a cross-linking agent for the silicone resin. an organopolysiloxane having at least two hydrogen atoms (SiH groups) bonded to silicon atoms, a peroxide as a thermal polymerization initiator, and a photosensitive platinum (Pt) catalyst, wherein the mixing ratio ((G) / (R)) of the organosilicone material (G) to the organosilicone resin (R) in the above-mentioned organosilicone-based resin as a whole is in the range of 40.0 / 60.0 to 56.0 / 44.0 in terms of mass ratio, and the above-mentioned organosilicone material (G) comprises an organopolysiloxane containing an alkenyl group bonded to a silicon atom; alk ), the content of the alkenyl groups bonded to the silicon atoms in the whole silicone resin is 7.0×10 -7 mol / g or more and 5.5×10-6 The range is below mol / g.
[0019] Here, it may be characterized in that the semiconductor material in which the plurality of semiconductor elements are sealed with the covering material made of silicone resin is pasted from the covering material side for use.
[0020] In addition, the characteristic can be set as that in the above-mentioned adhesive layer, the molar ratio (SiH group / alkenyl group bonded to silicon atoms) of the above-mentioned cross-linking agent contained in the above-mentioned adhesive composition to the content (total amount) of the above-mentioned alkenyl group bonded to silicon atoms in the above-mentioned silicone-based resin as a whole contained in the adhesive composition is greater than 2.0 and less than 10.0.
[0021] Furthermore, the adhesive layer may be characterized in that the content of the peroxide in the adhesive composition is in a range of 0.10 parts by mass or more and 3.00 parts by mass or less in terms of solid content relative to 100 parts by mass of the entire solid content of the silicone-based resin.
[0022] Furthermore, it may be characterized in that, in the adhesive layer, the peroxide is a diacyl peroxide.
[0023] In addition, it can be characterized in that in the adhesive layer, the content of the photosensitive platinum (Pt) catalyst in the adhesive composition is in the range of 0.10 mass parts or more and 3.00 mass parts or less in terms of solid content relative to 100 mass parts of the entire solid content of the silicone-based resin.
[0024] In addition, the adhesive layer may have a content of the alkenyl groups bonded to silicon atoms in the entire silicone resin of 2.9×10 -6 mol / g or more and 4.1×10 -6 The range is below mol / g.
[0025] Furthermore, the feature may be that all of the following conditions (a) to (c) are satisfied in terms of adhesive properties in accordance with JIS Z 0237 (2009).
[0026] (a) The adhesive force to the BA-SUS test plate before light irradiation is in the range of 2.8 N / 10 mm or more and 5.5 N / 10 mm or less.
[0027] (b) Regarding the value of the ball number in the inclined ball viscosity test (inclination angle 30°, temperature 23°C, relative humidity 50% RH), when the value of the ball number before light irradiation is set to BN0 and the value of the ball number after light irradiation is set to BN1, the relationship is BN0>BN1.
[0028] (c) In the holding strength test after light irradiation (temperature 40°C, relative humidity 33% RH, standing time 2880 minutes), the phenomenon of failure when dropped means that the interface between the adhesive layer and the BA-SUS test plate is peeled off, or the film does not drop in the holding strength test.
[0029] In addition, from another point of view, the manufacturing method of the semiconductor chip applicable to the present invention is a manufacturing method of the semiconductor chip comprising the following steps, namely: a pasting step, for a semiconductor element substrate having a plurality of the above-mentioned semiconductor elements sealed with a sealing resin composed of a silicone resin formed on the substrate, pasting the above-mentioned dicing adhesive tape from the sealing resin side; a cutting step, cutting the above-mentioned semiconductor element substrate to which the above-mentioned dicing adhesive tape is pasted into a plurality of semiconductor chips; an irradiation step, irradiating the above-mentioned dicing adhesive tape of the above-mentioned semiconductor element substrate with light; and a peeling step, peeling the above-mentioned dicing adhesive tape from the above-mentioned plurality of semiconductor chips.
[0030] Effects of the Invention
[0031] According to the present invention, there can be provided an adhesive tape for dicing and a method for manufacturing a semiconductor chip using the same. The adhesive tape for dicing has good adhesion and tackiness to a semiconductor material formed by coating a plurality of semiconductor elements with a coating material before light irradiation, and has good pickup properties for semiconductor chips when the semiconductor chips separated into pieces by dicing are peeled off after light irradiation, and also suppresses residual adhesive on the semiconductor chips. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] [ Figure 1 ] is a diagram showing an example of the structure of a dicing adhesive tape applicable to the present embodiment.
[0033] [ Figure 2 ](a) to (e) are diagrams showing a method for manufacturing a semiconductor chip using the adhesive tape of the present embodiment.
[0034] [ Figure 3 ] is a schematic diagram showing the relationship between the crosslinking density of the silicone resin in the adhesive layer and the result of the holding force test of the adhesive tape 1 (drop time). DETAILED DESCRIPTION
[0035] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0036] [Composition of adhesive tape]
[0037] Figure 1The present invention is a diagram showing an example of the structure of a dicing adhesive tape 1 (hereinafter referred to as adhesive tape 1) applicable to the present embodiment. The adhesive tape 1 of the present embodiment is used for dicing semiconductor materials as raw materials of semiconductor chips in the manufacturing process of semiconductor chips having semiconductor elements such as LEDs (Light Emitting Diodes) and power semiconductors.
[0038] like Figure 1 As shown, the adhesive tape 1 has a structure in which an adhesive layer 3 is laminated on a base material 2 .
[0039] It should be noted that, although not shown in the figure, the adhesive tape 1 may also include an anchor coat layer for improving the adhesion between the substrate 2 and the adhesive layer 3 as required. In addition, the surface of the substrate 2 (the surface on the opposite side of the surface facing the adhesive layer 3) may be subjected to surface treatment. Furthermore, the surface of the adhesive layer 3 (the surface on the opposite side of the surface facing the substrate 2) may also be provided with a release liner.
[0040] <Base material>
[0041] The substrate 2 of this embodiment is made of a material that can transmit ultraviolet light or the like. The material of the substrate 2 is not particularly limited as long as it can transmit ultraviolet light or the like, and for example, plastic that can transmit ultraviolet light or the like can be used. It should be noted that, here, the ultraviolet light or the like can be transmitted does not mean that the transmittance of ultraviolet light or the like is 100%, but that the light can be transmitted to the extent that the photosensitive platinum (Pt) catalyst described later contained in the adhesive layer 3 can promote the addition reaction of the silicone resin and the crosslinking agent.
[0042] As the material of the substrate 2, specifically, resin films such as polyethylene terephthalate, polyethylene naphthalate, polyphenylene sulfide, biaxially stretched polypropylene, aliphatic polyimide (transparent polyimide), polycycloolefin, fluorine resin, and polyolefin resin can be used. In addition, for example, a composite film obtained by laminating polyethylene terephthalate and a polyolefin resin film, a composite film obtained by further laminating these composite films with a resin film, and a resin film made into multiple layers by coextrusion can also be used for the substrate 2 according to the application.
[0043] Among them, as the substrate 2, it is preferable to use a material containing polyethylene terephthalate as a main component.
[0044] <Adhesive layer>
[0045] The adhesive layer 3 of the present embodiment is composed of an adhesive composition including a silicone resin obtained by mixing an organic silicone material (G) and a silicone resin (R), a cross-linking agent for the silicone resin having at least two hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule, a peroxide as a thermal polymerization initiator, and a photosensitive platinum (Pt) catalyst.
[0046] The silicone resin is composed of an organic silicone material (G alk ) and a mixed resin obtained by mixing "organic silicone material (G) composed of "organic silicone resin (R) composed of organic polysiloxane" in a predetermined ratio. Hereinafter, each component contained in the adhesive composition constituting the adhesive layer 3 will be described in turn.
[0047] (Silicone resin)
[0048] The organic silicone resin of the present embodiment is composed of an organic silicone material (G alk ) and the “organic silicone resin (R) composed of an organopolysiloxane” are mixed in a manner in which the organic silicone material (G) and the organic silicone resin (R) are mixed in a manner in which the mixing ratio ((G) / (R)) of the organic silicone material (G) and the organic silicone resin (R) is in a range of 40.0 / 60.0 to 56.0 / 44.0 in terms of mass ratio.
[0049] In addition, the content of alkenyl groups bonded to silicon atoms in the entire silicone resin is 7.0×10 -7 mol / g or more and 5.5×10 -6 mol / g or less, more preferably 2.9×10 -6 mol / g or more and 4.1×10 -5 Here, "mol / g" means "the amount of substance per 1g of solid content of the entire silicone-based resin".
[0050] If the content of alkenyl groups bonded to silicon atoms in the entire silicone resin is less than 7.0×10 -7mol / g, when the adhesive tape 1 is irradiated with ultraviolet light, the second-stage crosslinking reaction (addition reaction) between the alkenyl groups bonded to the silicon atoms of the organic silicone material and the hydrogen atoms (SiH groups) bonded to the silicon atoms of the crosslinking agent is insufficient to improve the crosslinking density, and the adhesive is difficult to solidify and the cohesive force is not easy to improve. In this case, the desired reduction in adhesion and the failure mode in the holding force test cannot be obtained. After the adhesive tape 1 is used for cutting semiconductor element substrates, when the obtained semiconductor chips are peeled off from the adhesive tape 1, there is a risk that the pickup of the singulated semiconductor chips will deteriorate, and there is a risk that residual adhesive will easily form on the semiconductor chips.
[0051] On the other hand, if the content of alkenyl groups bonded to silicon atoms in the entire silicone resin exceeds 5.5×10 - 6 mol / g, when the mixing ratio of the silicone rubber (G) in the silicone resin of the adhesive composition constituting the adhesive layer 3 is high, depending on the type and content of the thermal polymerization initiator, the curing (first stage cross-linking reaction) of the silicone resin in the stage before irradiation with ultraviolet light or the like is excessively carried out due to the thermal polymerization initiator, and the adhesive layer 3 sometimes becomes too hard. In this case, when the adhesive tape 1 is used for cutting semiconductor element substrates, etc., when the semiconductor element substrates, etc. are cut, the semiconductor chips, etc., which are cut pieces, may be easily peeled off from the adhesive tape 1 and scattered.
[0052] The content of alkenyl groups bonded to silicon atoms in the entire silicone resin can be calculated as follows: 1 The calculation is performed by measuring the H-NMR (nuclear magnetic resonance) spectrum and determining the resonance signal area (integrated value) of the alkenyl group. The details will be described later.
[0053] It should be noted that, as long as the "mixing ratio ((G) / (R)) of the silicone material (G) and the silicone resin (R)" and the "content of alkenyl groups bonded to silicon atoms" in the silicone-based resin of the present embodiment are within the above ranges, the silicone material (G) composed of an organopolysiloxane containing no alkenyl groups bonded to silicon atoms may also be included. 0 That is, the organic silicone material (G) may be an "organic silicone material (G) composed of an organopolysiloxane containing an alkenyl group bonded to a silicon atom". alk )" or a mixture of two or more thereof, or "organic silicone material composed of an organopolysiloxane containing an alkenyl group bonded to a silicon atom (G alk )" and "organic silicone material composed of an organopolysiloxane containing no alkenyl group bonded to a silicon atom (G 0 )" or a mixture of two or more thereof.
[0054] Hereinafter, the organic silicone material (G alk )", "organic silicone material composed of an organopolysiloxane containing no alkenyl group bonded to a silicon atom (G 0 )” and “organic silicone resin (R) composed of an organopolysiloxane containing no alkenyl group bonded to a silicon atom” are described in further detail.
[0055] It should be noted that in the following description, an organic silicone material (G alk ) is expressed as an organic silica gel containing alkenyl groups bonded to silicon atoms (G alk ), or simply expressed as organic silicone material (G alk Similarly, sometimes an organic silicone material (G 0 ) is expressed as an organic silicone material (G 0 ), or simply expressed as organic silicone material (G 0 ). Furthermore, the silicone resin (R) composed of an organopolysiloxane may be simply referred to as silicone resin (R).
[0056] (Organic silicone material composed of an organopolysiloxane containing alkenyl groups bonded to silicon atoms (G alk ))
[0057] The organic silicone material (G) composed of an organopolysiloxane containing alkenyl groups bonded to silicon atoms in this embodiment alk ) is not particularly limited as long as it is an organic silicone material commonly used as an addition reaction type silicone resin, that is, an organic silicone material containing at least two alkenyl groups bonded to silicon atoms in one molecule on average.
[0058] Specifically, as organic silica gel (G alk ), the content of alkenyl groups bonded to silicon atoms can be 1.0×10 -6 mol / g or more and 1.0×10 -1 In this embodiment, from the viewpoint of controlling the adhesive properties of the adhesive layer 3 or being easily available when using a commercial product, it is preferred to use an organic silicone material having an alkenyl group content bonded to a silicon atom of 1.7×10 -6 mol / g or more and 1.0×10 -2 mol / g or less. alk ) The content of alkenyl groups in the whole silicone resin mixed with the silicone material (G) and the silicone resin (R) is 7.0×10 -7mol / g or more and 5.5×10 -6 In the embodiment of the range of mol / g or less, one kind may be used alone, or two or more kinds may be used in combination.
[0059] As the organic silicone material (G alk The molecular structure of the organopolysiloxane containing an alkenyl group bonded to a silicon atom may include, for example, a linear structure in which the main chain portion is composed of diorganosiloxane repeating units, a structure in which a part of the molecular structure includes a branched chain, a branched structure, or a cyclic structure. Among them, the organopolysiloxane having a linear structure is preferred in terms of mechanical strength and physical properties of the adhesive after irradiation with ultraviolet light or the like.
[0060] Organic silicone rubber (G alk ) can be either oily or raw gel, but is preferably raw gel. In the case of oily, the organic silicone material (G alk ) is preferably 1,000 mPa·s or more at 25°C. If the viscosity is less than 1,000 mPa·s, the adhesive before and after irradiation with ultraviolet light or the like may not exhibit the desired adhesive properties, and the adhesion between the adhesive layer 3 and the substrate 2 may deteriorate. In the case of a raw glue, the organic silicone material (G alk ) is preferably 100,000 mPa·s or less when dissolved in toluene at a concentration of 30% by mass at 25°C. If the viscosity exceeds 100,000 mPa·s, stirring may become difficult when preparing the adhesive composition. It should be noted that the organic silicone material (G alk ) can be measured using a B-type rotational viscometer (using a BM-type rotor, the same applies hereinafter).
[0061] Organic silicone rubber (G alk ), for example, compounds represented by the following general formula (1) or general formula (2) can be mentioned, but are not limited to these.
[0062] [Chemistry 1]
[0063] R 1 (3-a) X a SiO-(R 1 XSiO) m -(R 1 2 SiO) n -SiR 1 (3-a) X a General formula (1)
[0064] [Chemistry 2]
[0065] R 1 2 (OH)SiO-(R 1 XSiO) m+2 -(R 1 2 SiO) n -SiR 1 2 (OH) General formula (2)
[0066] Here, in the above general formula (1) and general formula (2), R 1 are independently monovalent hydrocarbon groups without aliphatic unsaturated bonds, and X is an organic group containing an alkenyl group. a is an integer of 0 to 3, m is an integer of 0 or more, and n is an integer of 100 or more, but a and m are not 0 at the same time. As long as a is 0, m is an integer of 2 or more. m+n is an organic silicone material (G alk ) is a value when the viscosity at 25°C becomes 1,000 mPa·s or more.
[0067] As R 1 , preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 7 carbon atoms, without an aliphatic unsaturated bond. Examples thereof include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; and aryl groups such as phenyl and tolyl, and methyl or phenyl is particularly preferred.
[0068] As X, an organic group containing an alkenyl group having 2 to 10 carbon atoms is preferred. For example, vinyl, allyl, hexenyl, octenyl, acryloyl propyl, acryloyl methyl, methacryloyl propyl, acryloyloxy propyl, acryloyloxymethyl, methacryloyloxypropyl, methacryloyloxymethyl, cyclohexenylethyl, and vinyloxypropyl can be listed. Among them, lower alkenyl groups such as vinyl and allyl are preferred, and vinyl is particularly preferred from an industrial point of view. The bonding position of the alkenyl group is not particularly limited, and can be a molecular chain terminal, a molecular chain side chain, or both a molecular chain terminal and a molecular chain side chain.
[0069] The number of alkenyl groups varies within an appropriate range depending on the content of the silicone resin (R) composed of the organopolysiloxane contained in the silicone-based adhesive, the type and amount of the crosslinking agent, the balance with other added components, etc., and therefore cannot be generalized. For example, it is usually preferably in the range of 0.1 or more and 3.0 or less relative to 100 organic groups of the organopolysiloxane. And, within the range of this ratio, the molecular weight is adjusted in a manner to achieve the above-mentioned viscosity range, preferably in a manner that the number of the above-mentioned alkenyl groups in one molecule of the organopolysiloxane is at least two on average. If the number of alkenyl groups is less than 0.1 relative to 100 organic groups of the organopolysiloxane, when the adhesive tape 1 is irradiated with light such as ultraviolet rays, the organic silicone material (G alk ) and the hydrogen atoms (SiH groups) bonded to silicon atoms of the crosslinking agent for the silicone resin do not sufficiently increase the crosslinking density, so the adhesive is difficult to cure and the cohesive force is not easy to increase. In this case, the desired reduction in adhesive force and the failure mode in the holding force test cannot be obtained. After the adhesive tape 1 is used for cutting semiconductor element substrates, when the obtained semiconductor chips are peeled off from the adhesive tape 1, there is a risk that the pick-up properties of the singulated semiconductor chips will deteriorate, and there is a risk that residual adhesive will be easily generated on the semiconductor chips. On the other hand, if the number of alkenyl groups exceeds 3.0 with respect to 100 organic groups of the organopolysiloxane, when the mixing ratio of the silicone rubber (G) in the silicone resin of the adhesive composition constituting the adhesive layer 3 is high, depending on the type and content of the thermal polymerization initiator, the curing (first stage cross-linking reaction) of the silicone resin in the stage before irradiation with ultraviolet light or the like is excessively performed due to the thermal polymerization initiator, and the adhesive layer 3 sometimes becomes too hard. In this case, when the adhesive tape 1 is used for cutting semiconductor element substrates, etc., when the semiconductor element substrates, etc. are cut, the semiconductor chips, etc., which are cut pieces, may be easily peeled off from the adhesive tape 1 and scattered.
[0070] As such an organic silica gel material (G alk) include dimethylpolysiloxane terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methylvinylsiloxane copolymer terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methylphenylsiloxane copolymer terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, methylphenylpolysiloxane terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methylvinylsiloxane copolymer terminated with trimethylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methylvinylsiloxane·methylphenylsiloxane copolymer terminated with trimethylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methylhexenylsiloxane copolymer terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, and dimethylsiloxane·methylhexenylsiloxane copolymer terminated with dimethylhexenylsiloxane at both ends of the molecular chain.
[0071] (Organic silicone material composed of an organopolysiloxane containing no alkenyl group bonded to a silicon atom (G 0 ))
[0072] The organic silicone material (G) composed of an organopolysiloxane containing no alkenyl group bonded to a silicon atom in this embodiment 0 ) is not particularly limited as long as it is a substance generally used as a peroxide-curable silicone resin, that is, a substance that does not contain an alkenyl group bonded to a silicon atom.
[0073] As such an organic silica gel material (G 0 The molecular structure of the organopolysiloxane of ) may include, for example, a linear structure in which the main chain portion is composed of diorganosiloxane repeating units, a structure in which a part of the molecular structure includes a branched chain, a branched structure, or a cyclic structure.
[0074] Organic silicone rubber (G 0 ) can be either oily or raw gel, but is preferably raw gel. In the case of oily, the organic silicone material (G 0 ) is preferably 1,000 mPa·s or more at 25°C. When the viscosity is less than 1,000 mPa·s, the adhesive before and after irradiation with ultraviolet light or the like may not exhibit the desired adhesive properties, and the adhesion between the adhesive layer 3 and the substrate 2 may deteriorate. In the case of a raw gel, the organic silicone material (G 0) is preferably 100,000 mPa·s or less when dissolved in toluene at a concentration of 30% by mass at 25°C. If the viscosity exceeds 100,000 mPa·s, stirring during preparation of the adhesive composition may become difficult. It should be noted that the organic silicone material (G 0 ) can be measured using a B-type rotational viscometer.
[0075] Organic silicone rubber (G 0 ), for example, substances represented by the following general formula (3) or general formula (4) can be mentioned, but are not limited to these.
[0076] [Chemistry 3]
[0077] R 4 3 SiO-(R 4 2 SiO) t -SiR 4 3 General formula (3)
[0078] [Chemistry 4]
[0079] R 4 2 (OH)SiO-(R 4 2 SiO) t -SiR 4 2 (OH) General formula (4)
[0080] Here, in the above general formula (3) and general formula (4), R 4 are independently monovalent hydrocarbon groups without an aliphatic unsaturated bond, t is an integer greater than 100, and the organic silicone material (G 0 ) has a viscosity of 1,000 mPa·s or more at 25°C.
[0081] As R 4 , preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 7 carbon atoms, without an aliphatic unsaturated bond. Examples thereof include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; and aryl groups such as phenyl and tolyl, and methyl is particularly preferred.
[0082] (Organic silicone resin (R) composed of organopolysiloxane)
[0083] The organosilicon resin (R) composed of organopolysiloxane in this embodiment has R 2 3SiO 0.5 Unit (M unit) and SiO 2 The organopolysiloxane having a unit (Q unit) is generally a substance called MQ resin used in silicone adhesives. The silicone resin (R) composed of the organopolysiloxane basically has no alkenyl group in the molecule, and a conventionally known resin can be used. 2 is a monovalent hydrocarbon group having 1 to 10 carbon atoms, and examples of the above R 1 The organopolysiloxane constituting the silicone resin (R) preferably has R 2 3 SiO 0.5 Unit / SiO 2 The molar ratio of the unit is within the range of 0.5 to 1.7. 2 3 SiO 0.5 Unit and SiO 2 Unit. If R 2 3 SiO 0.5 Unit / SiO 2 If the molar ratio of the unit is less than 0.5, the adhesive force and tackiness of the obtained adhesive layer 3 may be reduced. 2 3 SiO 0.5 Unit / SiO 2 The molar ratio of the unit exceeds 1.7, and the adhesive force and the holding power of the adhesive layer 3 obtained are sometimes reduced. It should be noted that the organopolysiloxane constituting the silicone resin (R) may also have an OH group. In this case, relative to the gross mass of the organopolysiloxane, the content of the OH group is preferably below 4.0 mass %. If the content of the OH group exceeds 4.0 mass %, the curability of the adhesive may be reduced.
[0084] The above-mentioned organopolysiloxane may be used in combination of two or more kinds. In addition, the above-mentioned organopolysiloxane may have R 2 SiO 1.5 Unit (T unit) and / or R 2 2 SiO unit (D unit).
[0085] "Organic silicone material (G alk )", "organic silicone material composed of an organopolysiloxane containing no alkenyl group bonded to a silicon atom (G 0)" and "organic silicone resin (R) composed of an organopolysiloxane" can usually be simply mixed and used. In addition, in the case where the organopolysiloxane represented by the above general formula (2) is used as an organic silicone material (G) composed of an organopolysiloxane containing alkenyl groups bonded to silicon atoms, alk ), the organopolysiloxane represented by the general formula (4) is contained as an organic silicone material (G) composed of an organopolysiloxane having no alkenyl group bonded to a silicon atom. 0 ), as long as the characteristics of the present invention are not impaired, the organic silicone material (G alk ) and silicone resin (R), or silicone rubber (G 0 ) is used in the form of a (partial) condensation reaction product obtained by preliminarily reacting the organic silicone resin (R).
[0086] (Mixing ratio of silicone rubber material (G) and silicone resin (R) in the whole silicone resin ((G) / (R)))
[0087] In the whole silicone resin contained in the adhesive layer 3 of the present embodiment, the mixing ratio ((G) / (R)) of the silicone material (G) to the silicone resin (R) is in the range of 40.0 / 60.0 to 56.0 / 44.0 in terms of mass ratio. Here, when two or more silicone materials (G) are used in combination, the total amount of each silicone material (G) is regarded as the mass of the silicone material (G) in the whole silicone resin. For example, when the silicone materials (G) are used in combination, the total amount of each silicone material (G) is regarded as the mass of the silicone material (G) in the whole silicone resin. alk ) and organic silicone material (G 0 ) as the organic silicone material (G), the mass of the organic silicone material (G) in the entire silicone resin is the organic silicone material (G alk ) quality and organic silicone material (G 0 Similarly, when two or more silicone resins (R) are used in combination, the total amount of each silicone resin is regarded as the mass of the silicone resin (R) in the entire silicone-based resin.
[0088] In the whole silicone resin contained in the adhesive layer 3 of the present embodiment, if the mixing ratio ((G) / (R)) of the silicone material (G) and the silicone resin (R) is less than the lower limit of the above range, when the adhesive tape 1 is irradiated with ultraviolet light or the like, the second-stage crosslinking reaction (addition reaction) between the alkenyl group bonded to the silicon atom of the silicone material (G) and the hydrogen atom (SiH group) bonded to the silicon atom of the crosslinking agent for the silicone resin does not contribute sufficiently to the increase in crosslinking density, and the adhesive is difficult to cure and the cohesive force is not easy to increase. In this case, the desired reduction in adhesion and the failure mode in the holding force test cannot be obtained. After the adhesive tape 1 is used for cutting a semiconductor element substrate, etc., when the obtained semiconductor chip, etc. is peeled off from the adhesive tape 1, there is a risk that the pick-up property of the singulated semiconductor chip will deteriorate, and there is a risk that residual adhesive will easily form on the semiconductor chip, etc.
[0089] On the other hand, in the whole silicone resin contained in the adhesive layer 3 of the present embodiment, if the mixing ratio ((G) / (R)) of the silicone rubber material (G) to the silicone resin (R) exceeds the upper limit of the above range, the curing (first stage cross-linking reaction) of the silicone resin is excessively performed due to the thermal polymerization initiator in the stage before irradiation with ultraviolet light or the like, and the adhesive layer 3 may become too hard. In this case, when the adhesive tape 1 is used for cutting semiconductor element substrates or the like, when the semiconductor element substrates or the like are cut, the semiconductor chips or the like as cut pieces may be easily peeled off from the adhesive tape 1 and scattered.
[0090] In contrast, by setting the mixing ratio ((G) / (R)) of the silicone material (G) and the silicone resin (R) in the whole silicone resin contained in the adhesive layer 3 of the present embodiment to the range of 40.0 / 60.0 to 56.0 / 44.0, the following effects can be achieved. That is, in the stage before irradiation with light such as ultraviolet rays, the adhesive layer 3 is in a state where a portion of the silicone resin is crosslinked and cured (a first-stage crosslinking reaction) due to a thermal polymerization initiator, so that the adhesive layer 3 can be given an appropriate adhesive force and tackiness that will not cause the semiconductor chips or the like that are cut off to fly away when cut. On the other hand, after irradiation with light such as ultraviolet rays, the silicone resin of the adhesive layer 3 has a content of alkenyl groups bonded to silicon atoms in the whole silicone resin of 7.0×10 -7 mol / g or more and 5.5×10 -6mol / g or less, so the second-stage crosslinking reaction (addition reaction) between the alkenyl group bonded to the silicon atom of the organic silicone material (G) and the hydrogen atom (SiH group) bonded to the silicon atom of the crosslinking agent for the organic silicone resin is fully carried out. As a result, the curing of the adhesive layer 3 is further carried out, so that the crosslinking density becomes higher and the cohesive force is further improved, so that the desired adhesion reduction and the failure mode in the holding force test can be obtained. As a result, after the adhesive tape 1 is used for cutting semiconductor element substrates, etc., good pickup can be achieved when the obtained semiconductor chips, etc. are peeled off from the adhesive tape 1, and residual adhesive for the semiconductor chips, etc. can be suppressed.
[0091] In particular, the content of alkenyl groups bonded to silicon atoms in the entire silicone resin is preferably 2.9×10 - 6 mol / g or more and 4.1×10 -6 In this case, since the cohesive force of the adhesive layer 3 can be easily controlled, the adhesive tape 1 having more stable cutting characteristics can be realized.
[0092] In addition, as the silicone resin of the present invention, a resin prepared by appropriately combining and mixing the commercially available materials exemplified below can also be used. Here, "resin prepared by appropriately combining and mixing" means "a resin prepared by mixing the commercially available materials with the content of alkenyl groups bonded to silicon atoms in the entire silicone resin of the adhesive layer 3 of 7.0×10 -7 mol / g or more and 5.5×10 -6 The invention further comprises a resin prepared by appropriately combining and mixing the respective materials so that the mixing ratio ((G) / (R)) of the organic silicone material (G) to the organic silicone resin (R) is in the range of 40.0 / 60.0 to 56.0 / 44.0. Examples of the respective commercially available materials prepared by appropriately combining and mixing the respective materials include the following materials (1) to (4).
[0093] Examples of the silicone resin containing an alkenyl group bonded to a silicon atom include (1) a silicone rubber material (G alk ) and a silicone resin (R) mixed in a predetermined ratio, (2) a commercially available addition reaction type silicone adhesive made of a silicone rubber material (G alk ) as the main component of the addition reaction type silicone release agent. In addition, as the silicone resin that does not contain an alkenyl group bonded to a silicon atom, there can be cited (3) silicone rubber (G 0) and a silicone resin (R) are mixed in a predetermined ratio, or (4) a commercially available peroxide-curable silicone adhesive, or a single commercial silicone resin (R). In the present invention, when these commercially available materials are appropriately combined and mixed, it is preferred that at least the addition reaction type silicone release agent (2) is included, and it is more preferred that the addition reaction type silicone adhesive (1) is included in addition to the addition reaction type silicone adhesive.
[0094] As described above, as the silicone resin containing alkenyl groups bonded to silicon atoms, (1) a silicone rubber material (G alk ) and a silicone resin (R) are mixed in a predetermined ratio and are commercially available as an addition reaction type silicone adhesive; (2) a silicone rubber material (G alk ) as a main component of commercially available addition reaction type silicone-based release agents, etc. Specific commercially available materials are exemplified below.
[0095] (1) Addition reaction type silicone adhesive
[0096] As the above-mentioned commercially available addition reaction type silicone adhesive, there is no particular limitation as long as it is a silicone adhesive commonly used for silicone adhesive tapes. Specifically, for example, KR-3700, KR-3701, X-40-3237-1, X-40-3240, X-40-3291-1, X-40-3229, X-40-3270, X-40-3306 (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd., TSR1512, TSR1516, XR37-B9204 ( The types without adding a platinum (Pt) catalyst and a cross-linking agent described later are SD4580, SD4584, SD4585, SD4560, SD4564, SD4565, SD4570, SD4574, SD4575, SD4600PFC, SD4593, and DC7651ADHESIVE (all trade names) manufactured by Dow Corning Toray Industries, Ltd. It should be noted that the type with added cross-linking agent can also be used. When the content of hydrogen atoms (SiH groups) bonded to silicon atoms in the added cross-linking agent is unclear, the content can be determined by the following method. 1 It can be determined by analysis of H-NMR (nuclear magnetic resonance) spectroscopy or the like.
[0097] (2) Addition reaction type silicone release agent
[0098] The commercially available addition reaction type silicone release agent is not particularly limited as long as it is a release agent for silicone release films commonly used for adhesive tapes. Specifically, for example, LTC750A, LTC310, LTC300B (all trade names) manufactured by Dow Corning Toray Industries, Ltd., KS3600, KS778 (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd., TPR6710, TPR6700 (all trade names) manufactured by Momentive High-Tech Materials Co., Ltd., etc. can be used. In this case, any type without adding a crosslinking agent and a type with adding a crosslinking agent can also be used, and the content of hydrogen atoms (SiH groups) bonded to silicon atoms in the added crosslinking agent can be determined by 1 It can be determined by analysis of H-NMR (nuclear magnetic resonance) spectroscopy or the like.
[0099] When the mixing ratio of the silicone rubber material (G) and the silicone resin (R) in the commercially available addition reaction type silicone adhesive is unknown, the mixing ratio can be determined by 29 The molecular weight can be determined from the peak area ratio of the D unit to the Q unit (organic silica gel:organic silica resin=D unit:Q unit) by Si-NMR (nuclear magnetic resonance) spectroscopy. Alternatively, it can be determined from the ratio of each peak area measured by gel permeation chromatography (GPC).
[0100] As the silicone resin containing no alkenyl group bonded to a silicon atom, an organic silicone compound (G 0 ) and a silicone resin (R) are mixed at a predetermined ratio, a commercially available peroxide-curable silicone adhesive, a commercially available silicone resin (R) alone, etc. Specific commercially available materials are exemplified below.
[0101] (3) Peroxide-curable silicone adhesive
[0102] The commercially available peroxide-curable silicone adhesive is not particularly limited as long as it is a silicone adhesive commonly used for silicone adhesive tapes. Specifically, for example, KR-100 and KR-101-10 (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd., YR3340, YR3286, PSA610-SM, XR37-B6722, and YF3897 (all trade names) manufactured by Momentive Advanced Materials Co., Ltd., SH4280, SH4282, SE4200, BY24-717, BY24-715, and Q2-7735 (all trade names) manufactured by Dow Corning Toray Industries, Ltd., etc. can be cited.
[0103] (4) Silicone resin
[0104] Specific examples of the commercially available single silicone resin (R) include YF3800, XF3905, YF3057, YF3807, YF3802, YF3897, XC96-723, and 2DSILANOL FLUID (all trade names) manufactured by Momentive Performance Materials.
[0105] When the mixing ratio of the silicone rubber material (G) and the silicone resin (R) in the above-mentioned commercially available peroxide-curable silicone adhesive is unknown, the mixing ratio can be determined by 29 The peak area ratio of D unit to Q unit (organic silica gel:organic silica resin=D unit:Q unit) measured by Si-NMR (nuclear magnetic resonance) spectroscopy can be obtained. Alternatively, it can be obtained from the ratio of each peak area measured by gel permeation chromatography (GPC).
[0106] As described above, these commercially available silicone resins can be used as long as the content of alkenyl groups bonded to silicon atoms in the entire silicone resin of the adhesive layer 3 is 7.0×10 -7 mol / g or more and 5.5×10 -6 mol / g or less, and the mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) is in the range of 40.0 / 60.0 to 56.0 / 44.0. As a preferred embodiment of using these commercially available silicone resins, specifically, for example, (a) a silicone resin having an addition reaction type silicone release agent added to an addition reaction type silicone adhesive, and (b) a silicone resin having a peroxide curing silicone adhesive and / or a silicone resin (R) further added thereto can be used as the main component of the adhesive composition constituting the adhesive layer 3.
[0107] In the description of the present embodiment, “as a main component” means that the main component accounts for 75 parts by mass or more, preferably 90 parts by mass or more, and more preferably 95 parts by mass or more, based on 100 parts by mass of the solid content of the adhesive composition.
[0108] (Crosslinking agent)
[0109] The crosslinking agent in this embodiment functions as a crosslinking agent for the silicone adhesive by irradiating the adhesive layer 3 with light such as ultraviolet rays. That is, the crosslinking agent in this embodiment is used to crosslink the silicone material (G) contained in the silicone resin when the photosensitive platinum (Pt) catalyst in the silicone adhesive is activated by irradiating the adhesive layer 3 with light such as ultraviolet rays. alk) undergoes an addition reaction with the alkenyl groups bonded to the silicon atoms, thereby crosslinking the adhesive layer 3. The crosslinking agent crosslinks the silicone resin, and the adhesive layer 3 is cured, and the crosslinking density is increased, so that the cohesive force of the adhesive layer 3 is increased compared to before irradiation with ultraviolet light or the like.
[0110] As a crosslinking agent, an organopolysiloxane having at least two, preferably three or more hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule (organohydrogenpolysiloxane) is used. In the following description, an organopolysiloxane having hydrogen atoms (SiH groups) bonded to silicon atoms may be simply referred to as organohydrogenpolysiloxane.
[0111] The molecular structure of the organohydrogenpolysiloxane used as a crosslinking agent may be, for example, a linear structure, a linear structure having a portion of branches, a branched structure, or a network structure. The viscosity of the organohydrogenpolysiloxane at 25° C. is preferably in the range of 1 mPa·s to 5,000 mPa·s. The viscosity may be measured using a B-type rotational viscometer.
[0112] Conventionally known organohydrogenpolysiloxanes can be used as the crosslinking agent. For example, organohydrogenpolysiloxanes represented by the following general formula (5) or (6) are exemplified, but are not limited thereto.
[0113] [Chemistry 5]
[0114] H b R 3 (3-b) SiO-(HR 3 SiO) p -(R 3 2 SiO) q -SiR 3 (3-b) H b General formula (5)
[0115] [Chemistry 6]
[0116]
[0117] Here, in the general formula (5) and the general formula (6), R3 is a monovalent hydrocarbon group having 1 to 10 carbon atoms, b is 0 or 1, and p and q are integers and are values such that the viscosity of the organohydrogenpolysiloxane at 25° C. is 1 mPa·s or more and 5,000 mPa·s or less. r is an integer of 2 or more, s is an integer of 0 or more, and r+s≥3, preferably 8≥r+s≥3. The organohydrogenpolysiloxane may be a mixture of two or more.
[0118] R 3It is a monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 7 carbon atoms. Examples thereof include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl and tolyl; and alkenyl groups such as vinyl and allyl. Methyl and phenyl are particularly preferred.
[0119] The content of the organohydrogenpolysiloxane used as a crosslinking agent in the adhesive layer 3 of the present embodiment is determined by the organic silicone material (G alk ) and the content of silicon-bonded alkenyl groups of the organohydrogenpolysiloxane vary within an appropriate range and cannot be generalized, but it is generally preferred that the molar ratio of the content (total amount) of silicon-bonded hydrogen atoms (SiH groups) of the cross-linking agent contained in the adhesive composition constituting the adhesive layer 3 to the content (total amount) of silicon-bonded alkenyl groups of the organosilicon-based resin contained in the adhesive composition be an amount within a range of 2.0 to 10.0.
[0120] In the case where the content of the organohydrogenpolysiloxane is less than the above lower limit, when the adhesive tape 1 is irradiated with ultraviolet light or the like, the second-stage crosslinking reaction (addition reaction) between the alkenyl groups bonded to the silicon atoms of the organic silicone material and the hydrogen atoms (SiH groups) bonded to the silicon atoms of the crosslinking agent is insufficient to improve the crosslinking density, and the adhesive is difficult to cure and the cohesive force is not easy to improve. In this case, the desired reduction in adhesive force and the failure mode in the holding force test cannot be obtained. After the adhesive tape 1 is used for cutting semiconductor element substrates, etc., when the obtained semiconductor chips, etc. are peeled off from the adhesive tape 1, there is a risk that the pick-up properties of the singulated semiconductor chips will deteriorate, and there is a risk that residual adhesive will easily form on the semiconductor chips, etc.
[0121] On the other hand, when the content of the organohydrogenpolysiloxane exceeds the above upper limit, there is a risk that the unreacted organohydrogenpolysiloxane will contaminate the semiconductor chip. In addition, the hydrogen atoms (SiH groups) bonded to the silicon atoms in the unreacted organohydrogenpolysiloxane react with oxygen and moisture in the air to change into SiOH, and the adhesive force of the adhesive layer 3 relative to the adherend increases, and there is a risk that the pickup property of the semiconductor chip after being singulated will deteriorate.
[0122] As described above, the content of the crosslinking agent in the adhesive layer 3 of the present embodiment can be adjusted in such a manner that the molar ratio of the content (total amount) of hydrogen atoms (SiH groups) bonded to silicon atoms in the crosslinking agent as a whole in the adhesive layer 3 relative to the content (total amount) of alkenyl groups bonded to silicon atoms in the whole silicone resin falls within the above range. The content of the crosslinking agent that satisfies this range varies depending on the number of hydrogen atoms (SiH groups) bonded to silicon atoms possessed by the crosslinking agent. For example, the crosslinking agent can be added in such a manner that the solid content is in the range of 0.20 parts by mass or more and 20.00 parts by mass or less relative to 100 parts by mass of the solid content of the whole silicone resin contained in the adhesive composition constituting the adhesive layer 3.
[0123] By setting the content of the cross-linking agent for the silicone resin in the adhesive layer 3 to the above range, when the semiconductor chip is peeled off from the dicing adhesive tape, the adhesive layer 3 is irradiated with light such as ultraviolet rays, thereby activating the photosensitive platinum (Pt) catalyst in the silicone adhesive, thereby promoting the cross-linking of the silicone rubber material (G alk ) and the hydrogen atom (SiH group) bonded to the silicon atom of the crosslinking agent for the organic silicon resin, the crosslinking density becomes higher, and the cohesive force of the adhesive becomes larger than that before irradiation with ultraviolet light. As a result, the adhesive force of the adhesive layer 3 is appropriately reduced, and good pickup can be achieved when the semiconductor chip is peeled off from the adhesive tape 1, and residual adhesive on the semiconductor chip can be suppressed.
[0124] The crosslinking agent is not particularly limited as long as it is a substance commonly used as a crosslinking agent for addition reaction type silicone adhesives, that is, an organopolysiloxane (organohydrogenpolysiloxane) having at least two hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule. Specifically, examples thereof include X-92-122 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd. and BY24-741 (trade name) manufactured by Dow Corning Toray Industries, Ltd. It should be noted that when the content of hydrogen atoms (SiH groups) bonded to silicon atoms in these crosslinking agents is unclear, the content can be determined by the method described below. 1 It can be determined by analysis of H-NMR (nuclear magnetic resonance) spectroscopy or the like.
[0125] (Photosensitive platinum (Pt) catalyst)
[0126] The photosensitive platinum (Pt) catalyst is used to promote the curing caused by the addition reaction (hydrosilylation) of the silicone resin and the crosslinking agent constituting the adhesive layer 3 by irradiation with light such as ultraviolet rays. It can be used to promote the curing of the silicone rubber (G alkThe wavelength of the curing light caused by the addition reaction of the alkenyl group bonded to the silicon atom possessed by the cross-linking agent and the hydrogen atom (SiH group) bonded to the silicon atom possessed by the cross-linking agent is preferably in the range of not less than 240 nm and not more than 400 nm.
[0127] As the photosensitive platinum (Pt) catalyst, a photoactive cyclopentadienyl platinum (IV) compound is preferably used in view of good photosensitivity and reaction rate.
[0128] The photoactive cyclopentadienyl platinum (IV) compound is not particularly limited, and examples thereof include (cyclopentadienyl)dimethyltrimethylsilylmethylplatinum, (cyclopentadienyl)diethyltrimethylsilylmethylplatinum, (cyclopentadienyl)dipropyltrimethylsilylmethylplatinum, (cyclopentadienyl)diisopropyltrimethylsilylmethylplatinum, (cyclopentadienyl)diallyltrimethylsilylmethylplatinum, (cyclopentadienyl)dibenzyltrimethylsilylmethylplatinum, (cyclopentadienyl)dimethyltriethylsilylmethylplatinum, Alkyl methyl platinum, (cyclopentadienyl) dimethyl tripropyl silyl methyl platinum, (cyclopentadienyl) dimethyl triisopropyl silyl methyl platinum, (cyclopentadienyl) dimethyl triphenyl silyl methyl platinum, (cyclopentadienyl) dimethyl dimethyl phenyl silyl methyl platinum, (cyclopentadienyl) dimethyl methyl diphenyl silyl methyl platinum, (cyclopentadienyl) dimethyl dimethyl (trimethylsiloxy) silyl methyl platinum, (cyclopentadienyl) dimethyl dimethyl (dimethylvinylsiloxy) silyl alkyl methylplatinum, [(1'-naphthyl)cyclopentadienyl]trimethylsilylmethylplatinum, [(2'-naphthyl)cyclopentadienyl]trimethylsilylmethylplatinum, [1-methyl-3-(1'-naphthyl)cyclopentadienyl]trimethylsilylmethylplatinum, [1-methyl-3-(2'-naphthyl)cyclopentadienyl]trimethylsilylmethylplatinum, [(4'-biphenyl)cyclopentadienyl]trimethylsilylmethylplatinum, [1-(4'-biphenyl)-3-methylcyclopentadienyl]trimethylsilyl Methylplatinum, [(9'-phenanthrenyl)cyclopentadienyl]trimethylsilylmethylplatinum, [1-methyl-3-(9'-phenanthrenyl)cyclopentadienyl]trimethylsilylmethylplatinum, [1-(2'-anthryl)-3-methylcyclopentadienyl]trimethylsilylmethylplatinum, [(2'-anthryl)cyclopentadienyl]trimethylsilylmethylplatinum, [(1'-pyrenyl)cyclopentadienyl]trimethylsilylmethylplatinum, [1-methyl-3-(1'-pyrenyl)cyclopentadienyl]trimethylsilylmethylplatinum, and the like.
[0129] The cyclopentadienyl ring in the above compounds may also be substituted by methyl, chlorine, fluorine, trimethylsilyl, triethylsilyl, dimethylphenylsilyl, methyldiphenylsilyl, triphenylsilyl, phenyl, fluorophenyl, chlorophenyl, methoxy, naphthyl, biphenyl, anthracenyl, pyrene, 2-benzoylnaphthalene, thioxanthone, 2-chlorothioxanthone, 2-isopropylthioxanthone, anthraquinone, 1-chloroanthraquinone, acetophenone, benzophenone, 9,10-dimethylanthracene, 9,10-dichloroanthracene, and a cyclopentadienyl ring substituted by one or more groups selected from these groups.
[0130] In the above compounds, the cyclopentadienyl ring may be substituted by an η5-fluorenyl group.
[0131] The cyclopentadienyl ring in the above-mentioned compound is preferably an unsubstituted cyclopentadienyl ring, a cyclopentadienyl ring substituted with one or more aromatic organic groups, a cyclopentadienyl ring substituted with one or more aliphatic organic groups, or a cyclopentadienyl ring substituted with one or more aromatic organic groups and one or more aliphatic organic groups. In addition, the organic group that may be substituted with the cyclopentadienyl ring is preferably a naphthyl, a biphenylyl, an anthracenyl, a phenanthrenyl, and a pyrenyl.
[0132] The content of the photosensitive platinum (Pt) catalyst in the adhesive layer 3 of the present embodiment is as long as it can promote the silicone rubber (G) in the silicone adhesive by irradiation with light such as ultraviolet rays. alk) and the hydrogen atom (SiH group) bonded to the silicon atom possessed by the cross-linking agent. The content of the photosensitive platinum (Pt) catalyst in the adhesive layer 3 of the present embodiment is preferably in the range of 0.10 mass parts or more and 3.00 mass parts or less in terms of solid content relative to 100 mass parts of the solid content of the entire silicone resin in the adhesive composition constituting the adhesive layer 3, and more preferably in the range of 0.20 mass parts to 1.00 mass parts. When the content of the photosensitive platinum (Pt) catalyst is less than 0.10 mass parts, when the adhesive tape 1 is irradiated with light such as ultraviolet rays, the cross-linking reaction (addition reaction) between the alkenyl group bonded to the silicon atom possessed by the organic silicone material and the hydrogen atom (SiH group) bonded to the silicon atom possessed by the cross-linking agent cannot be fully carried out, the cross-linking density is not sufficiently increased, the adhesive is difficult to cure, and the cohesion is not easy to increase. In this case, the desired reduction in adhesive force and the failure mode in the holding force test cannot be obtained. After the adhesive tape 1 is used for cutting a semiconductor element substrate, when the obtained semiconductor chip is peeled off from the adhesive tape 1, there is a risk that the pick-up property of the single-chip semiconductor chip will deteriorate, and there is a risk that the semiconductor chip will easily produce residual adhesive. On the other hand, when the content of the photosensitive platinum (Pt) catalyst exceeds 3.00 parts by mass, since the above-mentioned cross-linking reaction (addition reaction) is fully carried out, even if the content is 10.0 parts by mass, there is no particular problem as the characteristics of the adhesive tape 1, but it is not preferred from the viewpoint of economic efficiency.
[0133] (Thermal polymerization initiator)
[0134] As the thermal polymerization initiator in the present embodiment, peroxide, more specifically organic peroxide can be used.The thermal polymerization initiator in the present embodiment is used to give the adhesive layer 3 of the adhesive tape 1 before irradiating ultraviolet light and other light, which will not produce the appropriate adhesion and tackiness of the semiconductor chips etc. as cut pieces when cutting.That is, the heat applied in the heating and drying process when forming the adhesive layer 3 is used to make the thermal polymerization initiator in the adhesive layer 3 produce free radicals.And, this free radical mainly attacks the methyl and alkenyl part of the organic silicone material (G) in the organic silicone resin to form a methylene chain, so that the adhesive layer 3 is appropriately crosslinked and cured.Specifically, it is believed that first methyl reacts with alkenyl, and at the same time or subsequently, methyl reacts with each other, crosslinked part and methyl.Thus, suitable cohesion can be given to the adhesive layer 3, and as a result, suitable adhesion and tackiness of the semiconductor chips etc. as cut pieces can be stably achieved when cutting.
[0135] The peroxide used as the thermal polymerization initiator is not particularly limited as long as it is a peroxide that decomposes to generate free oxygen radicals, and examples thereof include dibenzoyl peroxide, 4,4'-dimethyldibenzoyl peroxide, 3,3'-dimethyldibenzoyl peroxide, 2,2'-dimethyldibenzoyl peroxide, 2,2',4,4'-tetrachlorodibenzoyl peroxide, diisobutyryl peroxide, dilauroyl peroxide, diisononanoyl peroxide, and the like. Diacyl peroxides having a half-life temperature of 85°C to 135°C; dialkyl peroxides having a half-life temperature of 170°C to 200°C, such as diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,1′-di-tert-butylperoxy-3,3,5-trimethylenecyclohexane, and 1,3-di-(tert-butylperoxy)-diisopropylbenzene. Commercially available products include NYPER BMT-K40 and NYPER BW (both trade names) manufactured by NOF Corporation, and PERBUTYL C, PERCUMYL D, and PERBUTYLP (all trade names) manufactured by NOF Corporation.
[0136] The deformation temperature (heat resistance) of the base material 2 of the adhesive tape 1 and the organic silicone material (G alk ) from the perspective of the residual amount of alkenyl groups in the organic silicone material (G), the above-mentioned peroxide preferably uses a diacyl peroxide having a 1-minute half-life temperature of about 85°C to 135°C. That is, when a diacyl peroxide is used as the peroxide, compared with the case of using a dialkyl peroxide (having a 1-minute half-life temperature of about 170°C to 200°C), it can be decomposed even at a low heating temperature and a short drying time at which the base material 2 of the adhesive tape 1 is difficult to thermally deform in the heating and drying process when forming the adhesive layer 3. Furthermore, the reaction of the methyl groups of the organic silicone material (G) with each other is more likely to proceed than the reaction of the methyl groups of the organic silicone material (G) with the alkenyl groups, and when irradiated with light such as ultraviolet rays, the addition reaction (second-stage crosslinking reaction) with the hydrogen atoms (SiH groups) bonded to the silicon atoms of the crosslinking agent can better ensure the organic silicone material (G) required for further improving the crosslinking density of the adhesive layer 3. alk ) of the alkenyl residue.
[0137] The content of the thermal polymerization initiator in the adhesive layer 3 varies depending on the heating temperature and time, the decomposition temperature (1 minute half-life temperature) of the organic peroxide used, the mixing ratio of the silicone rubber material (G), etc., and therefore cannot be generalized. For example, the content of the thermal polymerization initiator is preferably in the range of 0.10 mass parts or more and 3.00 mass parts or less, more preferably in the range of 0.50 mass parts or more and 2.00 mass parts or less, and particularly preferably in the range of 0.70 mass parts or more and 1.80 mass parts or less, relative to 100 mass parts of the solid content of the organic silicone resin in the adhesive layer 3. If the content of the thermal polymerization initiator in the adhesive layer 3 is less than 0.10 mass parts in terms of solid content relative to 100 mass parts of the solid content of the organic silicone resin in the adhesive layer 3, the crosslinking and curing (first stage crosslinking reaction) of the organic silicone resin caused by the thermal polymerization initiator in the adhesive layer 3 becomes insufficient before irradiation with ultraviolet light or the like. Therefore, when the ratio of the organic silicone material (G) in the whole organic silicone resin is high, there is a risk that the adhesive layer 3 becomes soft due to the organic silicone material (G) component. In this case, when cutting the semiconductor element substrate, the vibration of the cutting is easily transmitted to the adhesive layer 3 and the amplitude becomes larger, for example, there is a risk that the semiconductor element substrate will shift from the reference position. Moreover, along with this, there is a risk of the semiconductor chip being broken into pieces (fragments), and there is a risk of large deviations on each semiconductor chip. In addition, the adhesion and viscosity of the adhesive layer 3 may also be reduced. In this case, when the adhesive tape 1 is used for cutting the semiconductor element substrate, when the semiconductor element substrate is cut, the semiconductor chip, etc., which is the cut piece, may be easily peeled off from the adhesive tape 1 and scattered.
[0138] On the other hand, if the content of the thermal polymerization initiator exceeds 3.00 parts by mass, the crosslinking and curing of the silicone resin (the first stage of the crosslinking reaction) is excessively performed due to the thermal polymerization initiator at the stage before irradiation with ultraviolet light or the like, depending on the type of the thermal polymerization initiator, the heating temperature and time, and sometimes the adhesive layer 3 becomes too hard. In this case, when the adhesive tape 1 is used for cutting semiconductor element substrates, etc., when the semiconductor element substrates, etc. are cut, the semiconductor chips, etc., which are cut pieces, may be easily peeled off from the adhesive tape 1 and scattered. In addition, the thermal polymerization initiator itself or the components derived from the decomposition products of the thermal polymerization initiator may remain in the adherend and contaminate the adherend.
[0139] The silicone adhesive layer of the present embodiment is composed of an adhesive composition including a silicone resin mixed with a silicone material (G) and a silicone resin (R) as a main component, an organopolysiloxane having at least two hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule as a crosslinking agent for the silicone resin, a peroxide as a thermal polymerization initiator, and a photosensitive platinum (Pt) catalyst, and may also contain other components within the range that does not impair the effect of the present invention. As other components, cohesion enhancers, reinforcing fillers, peeling control agents, etc. can be listed.
[0140] (Cohesion enhancing agent)
[0141] The cohesion enhancer is used as needed to enhance the cohesion of the adhesive layer 3. The cohesion enhancer is not particularly limited, and for example, a multifunctional thiol is used. As the cohesion enhancer composed of a multifunctional thiol, for example, KARENZ (registered trademark) MT-PE1 and KARENZ MT-NR1 manufactured by Showa Denko K.K. can be cited.
[0142] However, since the silicone resin and the multifunctional thiol in the adhesive composition constituting the adhesive layer 3 are incompatible, in order to use the multifunctional thiol as a cohesive force improving agent, a compatibilizing agent for the silicone resin and the multifunctional thiol must be used. The compatibilizing agent is not particularly limited, and examples thereof include KBM-802 and KBM-803 (both trade names) manufactured by Shin-Etsu Chemical Co., Ltd., which are silane coupling agents having a mercapto group, and SH6062 (trade name) manufactured by Dow Corning Toray Industries, Ltd., etc.
[0143] When a cohesive force enhancer is used in the adhesive layer 3, the amount of the cohesive force enhancer added is preferably in the range of 6 parts by mass or less in terms of solid content relative to 100 parts by mass of the solid content of the entire silicone resin. When the amount of the cohesive force enhancer added exceeds 6 parts by mass in terms of solid content relative to 100 parts by mass of the solid content of the entire silicone resin, even if a compatibilizing agent is added, the silicone resin and the polyfunctional thiol as the cohesive force enhancer may be phase-separated.
[0144] (Reinforcement filler)
[0145] The reinforcing filler is used as needed to improve the strength of the adhesive layer 3. The reinforcing filler is not particularly limited, and examples thereof include AEROSIL (registered trademark) 130, AEROSIL 200, and AEROSIL 300 manufactured by AEROSIL Co., Ltd. of Japan, REOLOSIL (registered trademark) QS-102 and REOLOSIL QS-30 manufactured by Tokuyama Co., Ltd., CARPLEX (registered trademark) 80 manufactured by DSL. Japan Co., Ltd., and Hi-Sil (registered trademark) -233-D manufactured by PPG.
[0146] (Peeling Control Agent)
[0147] The peeling control agent is used as needed to further reduce the adhesive force of the adhesive layer 3 after irradiation with ultraviolet light or the like. The peeling control agent is not particularly limited, and for example, light peeling additives such as silicone oil can be cited. However, when the amount of the peeling control agent added is large, there is a risk of contaminating the surface of the adherend due to seepage, so it is preferably added within a range where the contamination level of the adherend surface is within an allowable range.
[0148] <Thickness of adhesive layer>
[0149] The thickness of the adhesive layer 3 is preferably in the range of 10 μm or more and 100 μm or less, and more preferably in the range of 20 μm or more and 40 μm or less. When the thickness of the adhesive layer 3 is less than 10 μm, the adhesive force of the adhesive tape 1 is easily reduced due to the thinning of the thickness of the silicone adhesive contained in the adhesive layer 3. On the other hand, when the thickness of the adhesive layer 3 is thicker than 100 μm, cohesion failure of the adhesive layer 3 may easily occur. Moreover, after the adhesive tape 1 is used for cutting of semiconductor element substrates, etc., when the obtained semiconductor chips, etc. are peeled off from the adhesive tape 1, there is a risk that residual adhesive is easily generated on the semiconductor chips, etc. In addition, when cutting semiconductor element substrates, etc., the vibration of the cutting is easily transmitted to the adhesive layer 3 and the amplitude becomes larger, for example, there is a risk that the semiconductor element substrate is offset from the reference position. Moreover, along with this, there is a risk of fragments (fragments) on the singulated semiconductor chips, and there is a risk of large deviations on each single semiconductor chip.
[0150] <Adhesion coating>
[0151] As described above, in the adhesive tape 1 of the present embodiment, an adhesion-promoting coating matching the type of the substrate 2 may be provided between the substrate 2 and the adhesive layer 3, or a surface treatment such as a corona treatment may be performed, depending on the manufacturing conditions of the adhesive tape 1, the use conditions of the manufactured adhesive tape 1, etc. Thus, the adhesion between the substrate 2 and the adhesive layer 3 can be improved.
[0152] <Surface treatment>
[0153] The surface of the substrate 2 (the surface on the opposite side of the surface opposite to the adhesive layer 3) may also be subjected to a surface treatment such as a peeling improvement treatment. The treatment agent used for the surface treatment of the substrate 2 is not particularly limited, and for example, non-silicone-based peeling treatment agents such as long-chain alkyl vinyl monomer polymers, fluorinated alkyl vinyl monomer polymers, polyvinyl alcohol urethanes, and aminoalkyd resins may be used. As such non-silicone-based peeling treatment agents, for example, PEELOIL (registered trademark) 1050 and PEELOIL 1200 manufactured by Lion Specialty Chemicals Co., Ltd. may be cited.
[0154] <Release liner>
[0155] In addition, a release liner may be provided on the surface of the adhesive layer 3 (the surface opposite to the surface facing the substrate 2) as required. As the release liner, a release liner may be used which is a release liner on a film such as paper, polyethylene, polypropylene, polyethylene terephthalate, etc., to which a release treatment for improving the release property from the silicone-based adhesive contained in the adhesive layer 3 is applied. The material used in the release treatment of the release liner is not particularly limited, and for example, materials such as fluoroalkyl-modified silicone, long-chain alkyl vinyl monomer polymer, and aminoalkyd resin may be used.
[0156] <Adhesive tape thickness>
[0157] The thickness of the entire adhesive tape 1 having the above-described configuration is preferably in the range of 20 μm or more and 200 μm or less.
[0158] When the thickness of the adhesive tape 1 is less than 20 μm, when the adhesive tape 1 is used for dicing a semiconductor element substrate or the like, it may be difficult to peel the formed semiconductor chip or the like from the adhesive tape 1 .
[0159] On the other hand, when the thickness of the adhesive tape 1 exceeds 200 μm, it is difficult for the adhesive tape 1 to follow the unevenness formed on the adhesive surface of the semiconductor element substrate when the adhesive tape 1 is attached to the semiconductor element substrate. In this case, the bonding area between the adhesive tape 1 and the semiconductor element substrate becomes small, and semiconductor chips may be easily scattered during dicing.
[0160] [Manufacturing method of adhesive tape]
[0161] Next, a method for producing the adhesive tape 1 of the present embodiment will be described. It should be noted that the method for producing the adhesive tape 1 described below is an example, and the method for producing the adhesive tape 1 is not limited thereto.
[0162] When manufacturing the adhesive tape 1, first, the above-mentioned silicone adhesive, crosslinking agent, photosensitive platinum (Pt) catalyst and other components are dissolved in a general organic solvent such as toluene and ethyl acetate to obtain an adhesive solution. Then, the adhesive solution is applied to the surface of the substrate 2 that has been surface-treated and formed with an adhesion-enhancing coating as required using a notch wheel coater or the like in a manner to a predetermined thickness.
[0163] Next, the substrate 2 coated with the adhesive solution is heated in a drying furnace to dry and solidify the adhesive solution to form an adhesive layer 3. The conditions for heating and drying depend on the half-life temperature of the thermal polymerization initiator, etc., and therefore cannot be generalized. For example, the conditions disclosed in Japanese Patent Application Laid-Open No. 2012-107125 can be referred to. Specifically, for example, the adhesive solution for the adhesive layer 3 is applied to the substrate 2, and in the front half of the drying furnace, the temperature is gradually increased at 40 to 90° C. for initial drying, and then in the rear half of the drying furnace, the temperature is heated and dried for 1 to 5 minutes in the range of 120 to 200° C., and the original plate is wound in the form of a roll, but it is not limited to this.
[0164] Through the above process, we can obtain Figure 1 The adhesive tape 1 shown here includes an adhesive layer 3 laminated on a substrate 2. In the present embodiment, at this stage, the adhesive layer 3 is in a state where a portion of the silicone resin is crosslinked and cured by the thermal polymerization initiator (a first-stage crosslinking reaction).
[0165] [How to use adhesive tape]
[0166] The adhesive tape 1 of the present embodiment is used for dicing semiconductor materials, which are raw materials of semiconductor chips, in the manufacturing process of semiconductor chips having semiconductor elements such as LEDs (Light Emitting Diodes) and power semiconductors.
[0167] Specifically, the adhesive tape 1 is used to obtain individual semiconductor chips by cutting a semiconductor element substrate on which a plurality of semiconductor elements such as LED elements and power semiconductor elements are formed on a substrate made of resin, ceramic, etc. Here, for a semiconductor element substrate on which a plurality of semiconductor elements are formed, a sealing resin as an example of a covering material is sometimes provided in a manner of covering the semiconductor elements in order to protect the semiconductor elements from the influence of the external environment such as temperature and humidity.
[0168] The adhesive tape 1 of the present embodiment can be more preferably used for dicing a semiconductor element substrate provided with a sealing resin, in particular.
[0169] As a method for obtaining a plurality of semiconductor chips by cutting a semiconductor element substrate provided with a sealing resin, for example, the following method is conventionally known.
[0170] First, a dicing adhesive tape is attached to the substrate side of the semiconductor element substrate, and the semiconductor element substrate is cut from the side where the semiconductor element is formed using a dicing machine, etc. Then, each semiconductor chip formed by cutting is peeled off from the adhesive tape, thereby obtaining a plurality of semiconductor chips.
[0171] However, when the semiconductor element substrate is cut by sticking the dicing tape from the substrate side of the semiconductor element substrate, there are problems such as so-called edge collapse (ダレ) occurring on the cut surface (substrate side of the semiconductor chip) or the cut surface becoming rough.
[0172] Therefore, in recent years, in order to solve such a problem, the following method has been proposed, namely, to a semiconductor element substrate, a dicing adhesive tape is affixed from the side where the semiconductor element is formed, that is, the sealing resin side that seals the semiconductor element, rather than from the substrate side, and the semiconductor element substrate is cut.
[0173] Here, as a sealing resin for semiconductor elements such as LEDs and power semiconductors, epoxy resins with excellent electrical properties and heat resistance have been used in the past. However, epoxy resins have the following problems: they are prone to discoloration when used for high-output LEDs and power semiconductors, when used for short-wavelength LEDs, or due to the use environment of the semiconductor chip.
[0174] In contrast, silicone resins are less likely to be discolored by heat or light than epoxy resins, and in recent years, silicone resins are often used as sealing resins for semiconductor elements such as LEDs and power semiconductors. More specifically, silicone resins containing either or both of methyl and phenyl groups as functional groups, i.e., methyl-containing silicone resins, phenyl-containing silicone resins, and silicone resins containing both methyl and phenyl groups, are often used.
[0175] By using silicone resin as the sealing resin of the semiconductor element, the discoloration of the sealing resin caused by heat and light can be suppressed. In addition, the light transmittance of silicone resin is as high as over 88% (wavelength 400-800nm), and the refractive index can be adjusted within the range of over 1.41 and under 1.57. Therefore, in the case where the semiconductor element is an LED, by using a silicone resin with a higher refractive index as the sealing resin, the light emitted by the LED can be effectively extracted to the outside of the package. Among the above-mentioned silicone resins, by using a silicone resin containing phenyl, the refractive index of the sealing material can be further increased compared to the case of using a silicone resin containing methyl, thereby achieving further efficiency of the emitted light.
[0176] The methyl group-containing silicone resin is not particularly limited, and examples thereof include KER-2300, KER-2460, KER-2500N, KER-2600, KER-2700, KER-2900, and X-32-2528 (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd., and IVS4312, IVS4312, and XE14-C2042 manufactured by Momentive Advanced Materials Co., Ltd. , IVS4542, IVS4546, IVS4622, IVS4632, IVS4742, IVS4752, IVSG3445, IVSG0810, IVSG5778, XE13-C2479, IVSM4500 (all trade names), OE-6351, OE-6336, OE-6301 (all trade names) manufactured by Dow Corning Toray Industries, Ltd., etc.
[0177] The silicone resin containing a methyl group and a phenyl group is not particularly limited, and examples thereof include KER-6075, KER-6150, and KER-6020 (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd.
[0178] The phenyl-containing silicone resin is not particularly limited, and examples thereof include KER-6110, KER-6000, KER-6200, ASP-1111, ASP-1060, ASP-1120, and ASP-1050P (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd., XE14-C2508 (trade name) manufactured by Momentive High-Tech Materials Co., Ltd., and OE-6520, OE-6550, OE-6631, OE-6636, OE-6635, and OE-6630 (all trade names) manufactured by Dow Corning Toray Industries, Ltd.
[0179] Conventionally, as a dicing adhesive tape for cutting semiconductor elements, an adhesive tape having an adhesive layer composed of, for example, an acrylic resin-based adhesive has been used.
[0180] However, if such a conventional adhesive tape is adhered to the side of the semiconductor element substrate where the semiconductor element is formed (sealing resin side) and the semiconductor element substrate is cut, if, for example, the adhesion between the sealing resin and the adhesive tape is insufficient, problems such as semiconductor chips flying apart during cutting may occur.
[0181] In particular, the above-mentioned silicone resin has a property of high demoulding properties compared with epoxy resins and the like that have been used as sealing resins in the past. Therefore, for semiconductor element substrates using silicone resin as sealing resin, when an adhesive tape whose adhesive layer is composed of an acrylic resin-based adhesive is attached, the adhesive force between the silicone resin as sealing resin and the adhesive tape is likely to decrease. As a result, when cutting the semiconductor element substrate, it is more likely to cause problems such as the scattering of semiconductor chips.
[0182] In contrast, in the adhesive tape 1 of the present embodiment, the adhesive layer 3 is composed of an adhesive composition including an organic silicone resin having a predetermined amount of alkenyl groups bonded to silicon atoms and a thermal polymerization initiator, which is formed by mixing an organic silicone material (G) and an organic silicone resin (R) in an appropriate ratio, so that the adhesive layer 3 is in a state where a portion of the organic silicone resin is crosslinked and cured (a first-stage crosslinking reaction) due to the thermal polymerization initiator. Therefore, when cutting the semiconductor element substrate, even when the semiconductor element substrate is pasted from the sealing resin side composed of the organic silicone resin, the adhesion and viscous force between the semiconductor element substrate and the sealing resin can be stably and well maintained. In addition, compared with conventional adhesive tapes, when cutting the semiconductor element substrate, the generation of semiconductor chips flying around can be suppressed.
[0183] On the other hand, the adhesive composition constituting the adhesive layer 3 contains the above-mentioned silicone resin, a photosensitive platinum (Pt) catalyst, and a crosslinking agent, so that the photosensitive platinum (Pt) catalyst in the silicone resin is activated by irradiating light such as ultraviolet rays, thereby promoting the bonding of the organic silicone rubber (G alk ) and the hydrogen atoms (SiH groups) bonded to the silicon atoms of the cross-linking agent for the organic silicon resin, thereby increasing the cross-linking density. Therefore, the cohesive force of the adhesive is further increased compared to before irradiation with ultraviolet light or the like. As a result, the adhesive force of the adhesive layer 3 is appropriately reduced, and the failure mode in the further holding force test is "interface peeling" or "no falling" in the holding force test. As a result, good pickup when peeling the semiconductor chip from the adhesive tape 1 can be achieved, and residual adhesive on the semiconductor chip can be suppressed.
[0184] Hereinafter, a method of using the adhesive tape 1 of the present embodiment and a method of manufacturing a semiconductor chip using the adhesive tape 1 of the present embodiment will be described in detail. Figure 2 (a) to (e) are views showing a method for manufacturing a semiconductor chip using the adhesive tape 1 of the present embodiment.
[0185] It should be noted that the case of manufacturing a semiconductor chip having an LED element as a semiconductor element using the adhesive tape 1 is cited as an example for explanation. In addition, the method described below is an example of a method for using the adhesive tape 1 and a method for manufacturing a semiconductor chip using the adhesive tape 1, but is not limited to the following method.
[0186] In this embodiment, first, a plurality of semiconductor elements 102 are mounted on a substrate 101 made of, for example, a resin material, ceramics, etc., to produce a semiconductor element substrate 100. It should be noted that the semiconductor element 102 is, for example, an LED element, which is not shown in the figure, but is formed by stacking a plurality of semiconductor layers including, for example, a light-emitting layer that emits light when electricity is applied, and an electrode is formed on the upper portion.
[0187] Next, the plurality of semiconductor elements formed on the substrate 101 of the semiconductor element substrate 100 are sealed with a sealing resin 103 made of a silicone resin (sealing step). It should be noted that, in this example, the plurality of semiconductor elements 102 are sealed together with the sealing resin 103, but each semiconductor element 102 may be sealed separately with the sealing resin 103.
[0188] Then, if Figure 2 As shown in (a), the adhesive tape 1 and the semiconductor element substrate 100 are attached to each other so that the adhesive layer 3 of the adhesive tape 1 faces the sealing resin 103 of the semiconductor element substrate 100 (attaching step).
[0189] Then, if Figure 2 As shown in (b) and (c), the semiconductor element substrate 100 is cut along the predetermined cutting line X by a dicing machine or the like while the adhesive tape 1 is attached to the semiconductor element substrate 100 (cutting process). In this example, the semiconductor element substrate 100 to which the adhesive tape 1 is attached is cut from the substrate 101 side. Figure 2 As shown in (c), in this example, so-called full cutting is performed in which the semiconductor element substrate 100 is completely cut in the thickness direction.
[0190] Then, if Figure 2 As shown in (d), the adhesive tape 1 attached to the semiconductor element substrate 100 is irradiated with ultraviolet light or the like from the substrate 2 side (irradiation step). As described above, the substrate 2 is made of a material that can transmit ultraviolet light or the like. Therefore, by irradiating the adhesive tape 1 with ultraviolet light or the like from the substrate 2 side, the ultraviolet light or the like is transmitted through the substrate 2 and irradiated to the adhesive layer 3.
[0191] In the adhesive tape 1 of the present embodiment, since the adhesive layer 3 has a photosensitive platinum (Pt) catalyst, the photosensitive platinum (Pt) catalyst is activated by irradiating the adhesive layer 3 with light such as ultraviolet rays, thereby promoting the second-stage crosslinking reaction (addition reaction) between the silicone resin containing alkenyl groups bonded to silicon atoms and the crosslinking agent in the adhesive layer 3. As a result, the crosslinking density, that is, the cohesive force in the adhesive layer 3 is further increased compared to before irradiation with light such as ultraviolet rays, and the adhesive force of the adhesive layer 3 is reduced.
[0192] Next, the semiconductor chip 200 formed by cutting the semiconductor element substrate 100 is peeled off (picked up) from the adhesive tape 1, so that Figure 2 As shown in (e), the individualized semiconductor chips 200 can be obtained (peeling step).
[0193] As described above, in the adhesive tape 1 of the present embodiment, the adhesive layer 3 is composed of an adhesive composition including an organic silicone resin having a predetermined amount of alkenyl groups bonded to silicon atoms and a thermal polymerization initiator, which is obtained by mixing an organic silicone material (G) and an organic silicone resin (R) in an appropriate ratio. Thus, when the adhesive tape 1 is used for dicing, the adhesive force and tackiness between the adhesive tape 1 and the semiconductor element substrate 100 can be stably and well maintained.
[0194] In recent years, silicone resins with high mold release properties are often used as sealing resins 103 for sealing semiconductor elements 102. In contrast, the adhesive tape 1 of this embodiment has the above-described structure and thus has good adhesion and tack to the sealing resins 103 made of silicone resins.
[0195] As a result, when the adhesive tape 1 of the present embodiment is used for dicing the semiconductor element substrate 100 , it is possible to suppress the scattering of the semiconductor chips 200 .
[0196] Furthermore, the adhesive composition containing a silicone-based resin constituting the adhesive layer 3 of the adhesive tape 1 of the present embodiment has good adhesion to the sealing resin 103 as described above, and has a high releasability.
[0197] That is, the adhesive tape 1 of the present embodiment includes, for example, a photosensitive platinum (Pt) catalyst that promotes the addition reaction of the silicone resin containing alkenyl groups bonded to silicon atoms and the crosslinking agent in the adhesive layer 3 by irradiation with light such as ultraviolet rays. Moreover, by irradiating the adhesive layer 3 with light such as ultraviolet rays through the substrate 2 after the cutting process and before the stripping process, the photosensitive platinum (Pt) catalyst is activated, and the addition reaction of the silicone resin containing alkenyl groups bonded to silicon atoms and the crosslinking agent in the adhesive layer 3 is promoted. Compared with before irradiation with light such as ultraviolet rays, the crosslinking density in the adhesive layer 3 can be further increased, that is, the cohesive force is further increased, and the adhesive force of the adhesive layer 3 can be reduced. As a result, in the stripping process, when the semiconductor chip 200 obtained by cutting the semiconductor element substrate 100 is peeled off (picked up) from the adhesive tape 1, the generation of the so-called residual adhesive of the adhesive attached to the semiconductor chip 200 can be suppressed. In addition, good pick-up performance when the semiconductor chip 200 is peeled off from the adhesive tape 1 can be achieved.
[0198] It should be noted that the above description describes a method of attaching the adhesive tape 1 from the sealing resin side to a semiconductor element substrate having a plurality of semiconductor elements formed on the substrate and dicing the substrate to obtain individual semiconductor chips. However, the use of the adhesive tape 1 of this embodiment is not limited to this.
[0199] The adhesive tape 1 of this embodiment can also be used, for example, in the manufacture of chip-level packaged LEDs to obtain individual chip-level packaged LEDs by cutting a semiconductor material formed by coating a plurality of LED elements with a phosphor as an example of a coating material. It should be noted that the so-called phosphor is a member in which a fluorescent material is dispersed in a resin material, ceramic, or the like.
[0200] In recent years, with the miniaturization of chip-scale packaged LEDs, there is a tendency for the chip-scale packaged LEDs that have been singulated to be easily scattered during dicing. In contrast, by using the adhesive tape 1 of the present embodiment having the above-mentioned structure, the adhesion between the phosphor and the adhesive layer 3 can be well maintained, and the scattering of the chip-scale packaged LEDs that have been singulated can be suppressed.
[0201] Furthermore, by irradiating the adhesive layer 3 with light such as ultraviolet light after dicing to reduce the adhesive force, the individual chip-scale package LEDs can be easily peeled off from the adhesive tape 1 , and the generation of adhesive residue on the peeled chip-scale package LEDs can be suppressed.
[0202] Example
[0203] Next, the present invention will be described in more detail using Examples and Comparative Examples. It should be noted that the present invention is not limited to the following Examples.
[0204] In order to prepare various adhesive compositions used in the examples and comparative examples, the following silicone resins (a) to (j) were used as the main components of the adhesive compositions, and the following organopolysiloxanes having hydrogen atoms (SiH) bonded to silicon atoms (organohydrogenpolysiloxanes) (m) and (n) were used as crosslinking agents.
[0205] The silicone resins (a) to (d) are all silicone rubbers containing alkenyl groups bonded to silicon atoms. alk ) and an organic silicone resin (R), the mixing ratio and the content of alkenyl groups bonded to silicon atoms of which are different from each other. alk ) uses a dimethylsiloxane-methylvinylsiloxane copolymer having a molecular chain end-capped with dimethylvinylsiloxy groups having a weight average molecular weight (Mw) of about 500,000, and as the silicone resin (R) uses an R having a weight average molecular weight (Mw) of about 5,000. 2 3 SiO 0.5 Unit (M unit) and SiO 2 Unit (Q unit) of organopolysiloxane (MQ resin).
[0206] In addition, both the silicone resins (e) and (f) are silicone rubbers containing alkenyl groups bonded to silicon atoms (G alk ) of a single substance, the content of alkenyl groups bonded to silicon atoms is different from each other. alk ) using a dimethylsiloxane-methylhexenylsiloxane copolymer having a weight average molecular weight (Mw) of about 300,000 at both ends of the molecular chain and end-capped with dimethylhexenylsiloxy groups, for the silicone material (G alk ) used a dimethylsiloxane polymer having a weight average molecular weight (Mw) of about 200,000 and having dimethylvinylsiloxy groups terminated at both ends of the molecular chain.
[0207] Furthermore, the silicone resins (g) to (i) are all silicone rubber materials (G 0 ) and an organic silicone resin (R), the mixing ratios of which are different from each other. 0 ) uses a dimethylsiloxane polymer having a weight average molecular weight (Mw) of about 500,000, and for the silicone resin (R) uses an R having a weight average molecular weight (Mw) of about 5,000 2 3 SiO 0.5 Unit (M unit) and SiO 2 Unit (Q unit) of organopolysiloxane (MQ resin).
[0208] Furthermore, the silicone resin (j) is a single substance of the silicone resin (R), and the silicone resin (R) is a single substance having a weight average molecular weight (Mw) of about 5,000. 2 3 SiO 0.5 Unit (M unit) and SiO 2 Unit (Q unit) of organopolysiloxane (MQ resin).
[0209] Silicone resin (a)
[0210] Organic Silicone Material (G alk ) and a mixture of silicone resin (R)
[0211] (G alk ) / (R)=40.0 mass% / 60.0 mass%
[0212] Alkenyl (vinyl) content: 2.0×10 -6 mol / g
[0213] Silicone resin (b)
[0214] Organic Silicone Material (G alk ) and a mixture of silicone resin (R)
[0215] (G alk ) / (R)=35.0 mass% / 65.0 mass%
[0216] Alkenyl (vinyl) content: 1.8×10 -6 mol / g
[0217] · Silicone resin (c)
[0218] Organic Silicone Material (G alk ) and a mixture of silicone resin (R)
[0219] (G alk ) / (R)=50.0 mass% / 50.0 mass%
[0220] Alkenyl (vinyl) content: 2.5×10 -6 mol / g
[0221] Silicone resin (d)
[0222] Organic Silicone Material (G alk ) and a mixture of silicone resin (R)
[0223] (G alk ) / (R)=70.0 mass% / 30.0 mass%
[0224] Alkenyl (vinyl) content: 3.5×10 -6 mol / g
[0225] · Silicone resin (e)
[0226] Organic Silicone Material (G alk )monomer
[0227] Alkenyl (hexenyl) content: 2.0×10 -4 mol / g
[0228] Silicone resin (f)
[0229] Organic Silicone Material (G alk )monomer
[0230] Alkenyl (vinyl) content: 2.7×10 -3 mol / g
[0231] · Silicone resin (g)
[0232] Organic Silicone Material (G 0 ) and a mixture of silicone resin (R)
[0233] (G 0 ) / (R)=50.0 mass% / 50.0 mass%
[0234] No olefin
[0235] ·Silicone resin (h)
[0236] Organic Silicone Material (G 0 ) and a mixture of silicone resin (R)
[0237] (G 0 ) / (R)=40.0 mass% / 60.0 mass%
[0238] No olefin
[0239] Silicone resin (i)
[0240] Organic Silicone Material (G 0 ) and a mixture of silicone resin (R)
[0241] (G 0 ) / (R)=60.0 mass% / 40.0 mass%
[0242] No olefin
[0243] · Silicone resin (j)
[0244] Silicone resin (R) monomer
[0245] No olefin
[0246] Cross-linking agent (m)
[0247] Organohydrogenpolysiloxane
[0248] SiH group content: 2.0×10 -2 mol / g
[0249] Cross-linking agent (n)
[0250] Organohydrogenpolysiloxane
[0251] SiH group content: 2.4×10 -3 mol / g
[0252] It should be noted that the alkenyl content of the silicone resin and the SiH content of the crosslinking agent used above were measured by 500 MHz 1 Specifically, the non-volatile components of the silicone resin are fully dissolved in deuterated chloroform containing dimethyl sulfoxide as an internal standard sample, and the NMR device "JNM·ECA500" (product name) manufactured by JEOL Ltd. is used to measure the 1 H-NMR (nuclear magnetic resonance) spectrum. Next, the resonance signal area (integral value) of dimethyl sulfoxide, the internal standard sample, and the resonance signal area (integral value) of the alkenyl group in the measurement spectrum were determined, and the alkenyl group content per 1g of the silicone resin (solid content) was calculated based on the ratio. In addition, the SiH group content of the crosslinking agent was also determined in the same manner. 1 H-NMR spectrum, the resonance signal area (integral value) of dimethyl sulfoxide, the internal standard sample, and the resonance signal area (integral value) of SiH group in the measurement spectrum are obtained, and the content of SiH group per 1g of crosslinking agent (solid content) is calculated based on the ratio. It should be noted that when the crosslinking agent is added to the silicone resin from the beginning, as long as the crosslinking agent is added based on the ratio 1 The contents of alkenyl groups and SiH groups can be calculated simultaneously from the H-NMR spectrum.
[0253] 1. Production of adhesive tape
[0254] (Example 1)
[0255] <Preparation of silicone resin solution>
[0256] The silicone resin (S1) prepared by mixing the silicone resin (e), the silicone resin (g) and the silicone resin (j) in a mass ratio (e) / (g) / (j) of 2.72 / 83.43 / 13.85 was diluted and stirred with toluene to prepare a silicone resin (S1) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone material (G) and the silicone resin (R) in the silicone resin (S1) was 44.4 / 55.6, and the alkenyl content was 5.4×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (e) alk )" and "organic silicone resin (g) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (g)” and the “silicone resin (R) of the silicone-based resin (j)”.
[0257] <Preparation of cross-linking agent solution>
[0258] Next, a crosslinking agent (C1) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 8.82 / 91.18 was diluted and stirred with toluene to prepare a crosslinking agent (C1) solution (solid content concentration 20 mass %). The SiH group content of the crosslinking agent (C1) was 4.0×10 -3 mol / g.
[0259] <Preparation of adhesive solution>
[0260] Next, 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S1) solution were mixed with 3.00 parts by mass (0.60 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 4.4) of a crosslinking agent (C1) solution, 4.18 parts by mass (1.67 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] "NYPER BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to mix 4.47 parts by mass (0.67 parts by mass as solid content) of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by SigmaAldrich Japan Co., Ltd. with toluene to a solution having a solid content concentration of 15% by mass, and stir and mix evenly to prepare a coating adhesive solution.
[0261] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further, dried for 3 minutes in a heat treatment area having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was bonded to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 58 μm after drying was obtained.
[0262] (Example 2)
[0263] <Preparation of silicone resin solution>
[0264] The silicone resin (S2) prepared by mixing the silicone resin (e), the silicone resin (h) and the silicone resin (j) in a mass ratio (e) / (h) / (j) of 1.19 / 96.99 / 1.82 was diluted and stirred with toluene to prepare a silicone resin (S2) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S2) was 40.0 / 60.0, and the alkenyl content was 2.4×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (e) alk )" and "organic silicone resin (h) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (h)” and the “silicone resin (R) of the silicone-based resin (j)”.
[0265] <Preparation of cross-linking agent solution>
[0266] Next, a crosslinking agent (C2) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 2.83 / 97.17 was diluted and stirred with toluene to prepare a crosslinking agent (C2) solution (solid content concentration 20 mass %). The SiH group content of the crosslinking agent (C2) was 2.9×10 -3 mol / g.
[0267] <Preparation of adhesive solution>
[0268] Next, 4.10 parts by mass (0.82 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 10.0) of a crosslinking agent (C2) solution and 3.85 parts by mass (1.54 parts by mass in terms of solid content, solid content concentration 40%) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S2) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to prepare a solution having a solid content concentration of 15% by weight of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by SigmaAldrich Japan Co., Ltd. diluted with toluene to a solid content concentration of 6.47 parts by weight (0.97 parts by weight as solid content), and stir and mix evenly to prepare a coating adhesive solution.
[0269] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 12 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further, dried for 3 minutes in a heat treatment area having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 10 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was bonded to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 22 μm after drying was obtained.
[0270] (Example 3)
[0271] <Preparation of silicone resin solution>
[0272] The silicone resin (S3) prepared by mixing the silicone resin (e), the silicone resin (g) and the silicone resin (j) in a mass ratio (e) / (g) / (j) of 2.09 / 87.26 / 10.65 was diluted and stirred with toluene to prepare a silicone resin (S3) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S3) was 45.7 / 54.3, and the alkenyl content was 4.2×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (e) alk )" and "organic silicone resin (g) organic silicone material (G 0The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (g)” and the “silicone resin (R) of the silicone-based resin (j)”.
[0273] <Preparation of cross-linking agent solution>
[0274] Next, a crosslinking agent (C3) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 9.63 / 90.37 was diluted and stirred with toluene to prepare a crosslinking agent (C3) solution (solid content concentration 20% by mass). The SiH group content of the crosslinking agent (C3) was 4.1×10 -3 mol / g.
[0275] <Preparation of adhesive solution>
[0276] Next, 2.10 parts by mass (0.42 parts by mass in terms of solid content, SiH group / olefin molar ratio = 4.2) of a crosslinking agent (C3) solution and 4.38 parts by mass (1.75 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S3) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to prepare a solution having a solid content concentration of 15% by mass by diluting 3.13 parts by mass (0.47 parts by mass as solid content) of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by SigmaAldrich Japan Co., Ltd. with toluene, and stir and mix evenly to prepare a coating adhesive solution.
[0277] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 50 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment area having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 40 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 90 μm after drying was obtained.
[0278] (Example 4)
[0279] <Preparation of silicone resin solution>
[0280] The silicone resin (S4) prepared by mixing the silicone resin (b), the silicone resin (e) and the silicone resin (g) in a mass ratio of (b) / (e) / (g) of 49.51 / 0.97 / 49.52 was diluted and stirred with toluene to prepare a silicone resin (S4) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S4) was 43.1 / 56.9, and the alkenyl content was 2.8×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (b)". alk )”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (g) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (b)” and the “silicone resin (R) of the silicone-based resin (g)”.
[0281] <Preparation of cross-linking agent solution>
[0282] Next, a crosslinking agent (C4) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 5.50 / 94.50 was diluted and stirred with toluene to prepare a crosslinking agent (C4) solution (solid content concentration 20 mass %). The SiH group content of the crosslinking agent (C4) was 3.4×10 -3 mol / g.
[0283] <Preparation of adhesive solution>
[0284] Next, 1.75 parts by mass (0.35 parts by mass in terms of solid content, SiH group / olefin molar ratio = 4.1) of a crosslinking agent (C4) solution and 2.48 parts by mass (0.99 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S4) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to prepare a solution having a solid content concentration of 15% by mass by diluting 2.67 parts by mass (0.40 parts by mass as solid content) of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by Sigma-Aldrich Japan Contract Co., Ltd. with toluene, and stir and mix evenly to prepare a coating adhesive solution.
[0285] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 125 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was bonded to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 145 μm after drying was obtained.
[0286] (Example 5)
[0287] A silicone resin (S5) solution was prepared as described below. In the preparation of the adhesive solution, the silicone resin (S4) solution was changed to a silicone resin (S5) solution, the amount of the cross-linking agent (C4) solution was changed to 2.10 parts by mass (0.42 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 4.1), the amount of the organic peroxide solution was changed to 1.93 parts by mass (0.77 parts by mass in terms of solid content), the amount of the photosensitive platinum (Pt) catalyst solution was changed to 3.20 parts by mass (0.48 parts by mass in terms of solid content), and the thickness of the adhesive layer 3 after drying was changed to 38 μm. Except for this, the same operation as in Example 4 was performed to obtain an adhesive tape 1 with a total thickness of 58 μm after drying.
[0288] <Preparation of silicone resin solution>
[0289] The silicone resin (S5) prepared by mixing the silicone resin (b), the silicone resin (e) and the silicone resin (g) in a mass ratio of (b) / (e) / (g) of 60.37 / 1.18 / 38.45 was diluted and stirred with toluene to prepare a silicone resin (S5) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S5) was 41.5 / 58.5, and the alkenyl content was 3.4×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (b)". alk )”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (g) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (b)” and the “silicone resin (R) of the silicone-based resin (g)”.
[0290] (Example 6)
[0291] The silicone resin (S6) solution was prepared as described below. In the preparation of the adhesive solution, the silicone resin (S5) solution was changed to a silicone resin (S6) solution, the amount of the crosslinking agent (C4) solution was changed to 1.40 parts by mass (0.28 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 4.1), the amount of the organic peroxide solution was changed to 2.98 parts by mass (1.19 parts by mass in terms of solid content), and the amount of the photosensitive platinum (Pt) catalyst solution was changed to 2.13 parts by mass (0.32 parts by mass in terms of solid content). Except for this, the same operation as in Example 5 was carried out to obtain an adhesive tape 1 having a total thickness of 58 μm after drying.
[0292] <Preparation of silicone resin solution>
[0293] The silicone resin (S6) prepared by mixing the silicone resin (b), the silicone resin (e) and the silicone resin (g) in a mass ratio of (b) / (e) / (g) of 39.69 / 0.78 / 59.53 was diluted and stirred with toluene to prepare a silicone resin (S6) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S6) was 44.4 / 55.6, and the alkenyl content was 2.3×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (b)". alk)”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (g) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (b)” and the “silicone resin (R) of the silicone-based resin (g)”.
[0294] (Example 7)
[0295] The silicone resin (S7) solution was prepared as described below. In the preparation of the adhesive solution, the silicone resin (S5) solution was changed to a silicone resin (S7) solution, the amount of the crosslinking agent (C4) solution was changed to 1.75 parts by mass (0.35 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 4.0), the amount of the organic peroxide solution was changed to 2.48 parts by mass (0.99 parts by mass in terms of solid content), and the amount of the photosensitive platinum (Pt) catalyst solution was changed to 2.67 parts by mass (0.40 parts by mass in terms of solid content). Except for this, the same operation as in Example 5 was carried out to obtain an adhesive tape 1 having a total thickness of 58 μm after drying.
[0296] <Preparation of silicone resin solution>
[0297] A silicone resin (S7) prepared by mixing silicone resin (a), silicone resin (e) and silicone resin (g) in a mass ratio of (a) / (e) / (g) of 49.51 / 0.98 / 49.51 was diluted and stirred with toluene to prepare a silicone resin (S7) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S7) was 45.5 / 54.5, and the alkenyl content was 2.9×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (a)". alk )”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (g) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (a)” and the “silicone resin (R) of the silicone-based resin (g)”.
[0298] (Example 8)
[0299] A silicone resin (S8) solution was prepared as described below. In the preparation of the adhesive solution, the silicone resin (S5) solution was changed to a silicone resin (S8) solution, the amount of the crosslinking agent (C4) solution was changed to 1.40 parts by mass (0.28 parts by mass as solid content, SiH group / olefin molar ratio = 3.7), the amount of the organic peroxide solution was changed to 2.95 parts by mass (1.18 parts by mass as solid content), and the amount of the photosensitive platinum (Pt) catalyst solution was changed to 2.13 parts by mass (0.32 parts by mass as solid content). Except for this, the same operation as in Example 5 was carried out to obtain an adhesive tape 1 with a total thickness of 58 μm after drying.
[0300] <Preparation of silicone resin solution>
[0301] A silicone resin (S8) prepared by mixing silicone resin (c), silicone resin (e), silicone resin (h) and silicone resin (j) in a mass ratio of (c) / (e) / (h) / (j) of 39.46 / 0.77 / 59.18 / 0.59 was diluted and stirred with toluene to prepare a silicone resin (S8) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S8) was 56.0 / 44.0, and the alkenyl content was 2.5×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (c) alk )”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (h) organic silicone material (G 0 )”. In addition, the total mass of the silicone resin (R) is the total amount of “the silicone resin (R) of the silicone-based resin (c)”, “the silicone resin (R) of the silicone-based resin (h)” and “the silicone resin (R) of the silicone-based resin (j)”.
[0302] (Example 9)
[0303] <Preparation of silicone resin solution>
[0304] A silicone resin (S9) prepared by mixing silicone resin (b), silicone resin (e), silicone resin (g) and silicone resin (j) in a mass ratio of (b) / (e) / (g) / (j) of 33.14 / 0.07 / 66.29 / 0.50 was diluted and stirred with toluene to prepare a silicone resin (S9) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S9) was 44.8 / 55.2, and the alkenyl content was 7.1×10 -7 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (b)". alk )”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (g) organic silicone material (G 0 )”. In addition, the total mass of the silicone resin (R) is the total amount of “the silicone resin (R) of the silicone-based resin (b)”, “the silicone resin (R) of the silicone-based resin (g)” and “the silicone resin (R) of the silicone-based resin (j)”.
[0305] <Preparation of cross-linking agent solution>
[0306] Next, a crosslinking agent (C5) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 0.58 / 99.42 was diluted and stirred with toluene to prepare a crosslinking agent (C5) solution (solid content concentration 20% by mass). The SiH group content of the crosslinking agent (C5) was 2.5×10 -3 mol / g.
[0307] <Preparation of adhesive solution>
[0308] Next, 1.10 parts by mass (0.22 parts by mass in terms of solid content, SiH group / olefin molar ratio = 7.8) of a crosslinking agent (C5) solution and 2.90 parts by mass (1.16 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S9) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to mix 1.80 parts by mass (0.27 parts by mass as solid content) of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by SigmaAldrich Japan Co., Ltd. with toluene to a solution having a solid content concentration of 15% by mass, and stir and mix evenly to prepare a coating adhesive solution.
[0309] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 25 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 63 μm after drying was obtained.
[0310] (Example 10)
[0311] <Preparation of silicone resin solution>
[0312] The silicone resin (S10) prepared by mixing the silicone resin (c), the silicone resin (e), the silicone resin (g) and the silicone resin (j) in a mass ratio of (c) / (e) / (g) / (j) of 48.91 / 1.45 / 48.91 / 0.73 was diluted and stirred with toluene to prepare a silicone resin (S10) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S10) was 50.4 / 49.6, and the alkenyl content was 4.1×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (c) alk )”, “organic silicone resin (e) organic silicone material (Galk )" and "organic silicone resin (g) organic silicone material (G 0 )”. In addition, the total mass of the silicone resin (R) is the total amount of “the silicone resin (R) of the silicone-based resin (c)”, “the silicone resin (R) of the silicone-based resin (g)” and “the silicone resin (R) of the silicone-based resin (j)”.
[0313] <Preparation of cross-linking agent solution>
[0314] Next, a crosslinking agent (C6) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 8.04 / 91.9 was diluted and stirred with toluene to prepare a crosslinking agent (C6) solution (solid content concentration 20 mass %). The SiH group content of the crosslinking agent (C6) was 3.8×10 -3 mol / g.
[0315] <Preparation of adhesive solution>
[0316] Next, 1.75 parts by mass (0.35 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 3.3) of a crosslinking agent (C6) solution and 1.83 parts by mass (0.73 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S10) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to prepare a solution having a solid content concentration of 15% by weight of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by SigmaAldrich Japan Co., Ltd. diluted with toluene to a solid content concentration of 2.60 parts by weight (0.39 parts by weight in terms of solid content), and stir and mix evenly to prepare a coating adhesive solution.
[0317] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 58 μm after drying was obtained.
[0318] (Comparative Example 1)
[0319] A silicone resin (S11) solution is prepared as described below, the silicone resin (S1) solution is changed to a silicone resin (S11) solution, in the preparation of the adhesive solution, no cross-linking agent and organic peroxide are added, the amount of the photosensitive platinum (Pt) catalyst solution is changed to 5.33 parts by mass (0.80 parts by mass as solid content), the thickness of the adhesive layer 3 after drying is changed to 35 μm, and except for this, the same operation as in Example 1 is performed to obtain an adhesive tape 1 with a total thickness of 73 μm after drying.
[0320] <Preparation of silicone resin solution>
[0321] A silicone resin (S11) prepared by mixing a silicone resin (a) and a silicone resin (f) at a mass ratio (a) / (f) of 99.90 / 0.10 was diluted and stirred with toluene to prepare a silicone resin (S11) solution (solid content concentration 30% by mass). The silicone resin (S11) had a mixing ratio ((G) / (R)) of 40.1 / 59.9 for the silicone rubber material (G) and the silicone resin (R), and an olefin content of 4.7×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (a)". alk )" and "organic silicone resin (f) organic silicone material (G alk In addition, the total mass of the silicone resin (R) is the amount of the silicone resin (R) in the silicone-based resin (a).
[0322] (Comparative Example 2)
[0323] <Preparation of silicone resin solution>
[0324] The silicone resin (S12) prepared by mixing the silicone resin (b), the silicone resin (e) and the silicone resin (g) in a mass ratio of (b) / (e) / (g) of 49.28 / 1.45 / 49.28 was diluted and stirred with toluene to prepare a silicone resin (S12) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S12) was 43.3 / 56.7, and the alkenyl content was 3.8×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (b)". alk )”, “organic silicone resin (e) organic silicone material (G alk)" and "organic silicone resin (g) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (b)” and the “silicone resin (R) of the silicone-based resin (g)”.
[0325] <Preparation of cross-linking agent solution>
[0326] Next, in the same manner as in Example 10, a crosslinking agent (C6) solution (solid content concentration: 20% by mass) was prepared.
[0327] <Preparation of adhesive solution>
[0328] Next, 1.75 parts by mass (0.35 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 3.6) of a crosslinking agent (C6) solution and 2.48 parts by mass (0.99 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S12) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stirred and mixed uniformly. Then, 2.96 parts by mass (0.74 parts by mass in terms of solid content) of a solution of a platinum (Pt) metal catalyst "NC-25" (trade name, solid content concentration 25% by mass) manufactured by Dow Corning Toray Industries, Ltd. was added using a disperser, and stirred and mixed uniformly to prepare a coating adhesive solution.
[0329] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 58 μm after drying was obtained.
[0330] (Comparative Example 3)
[0331] <Preparation of silicone resin solution>
[0332] The silicone resin (S13) prepared by mixing the silicone resin (e) and the silicone resin (h) in a mass ratio (e) / (h) of 0.26 / 99.74 was diluted and stirred with toluene to prepare a silicone resin (S13) solution (solid content concentration 30% by mass). The silicone resin (S13) had a mixing ratio ((G) / (R)) of 40.2 / 59.8 for the silicone rubber material (G) and the silicone resin (R), and an olefin content of 5.2×10 -7 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (e) alk )" and "organic silicone resin (h) organic silicone material (G 0 In addition, the total mass of the silicone resin (R) is the amount of the silicone resin (R) in the silicone-based resin (h).
[0333] <Preparation of cross-linking agent solution>
[0334] Next, a crosslinking agent (C7) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 1.15 / 98.85 was diluted and stirred with toluene to prepare a crosslinking agent (C7) solution (solid content concentration 20 mass %). The SiH group content of the crosslinking agent (C7) was 2.6×10 -3 mol / g.
[0335] <Preparation of adhesive solution>
[0336] Next, 2.20 parts by mass (0.44 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 22.2) of a crosslinking agent (C7) solution and 4.98 parts by mass (1.99 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S13) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to prepare a solution having a solid content concentration of 15% by mass by diluting 3.53 parts by mass (0.53 parts by mass as solid content) of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by SigmaAldrich Japan Co., Ltd. with toluene, and stir and mix evenly to prepare a coating adhesive solution.
[0337] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 58 μm after drying was obtained.
[0338] (Comparative Example 4)
[0339] <Preparation of silicone resin solution>
[0340] The silicone resin (S14) prepared by mixing the silicone resin (e), the silicone resin (i) and the silicone resin (j) in a mass ratio of (e) / (i) / (j) of 4.67 / 79.44 / 15.89 was diluted and stirred with toluene to prepare a silicone resin (S14) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S14) was 52.3 / 47.7, and the alkenyl content was 9.4×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (e) alk )" and "organic silicone resin (i) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (i)” and the “silicone resin (R) of the silicone-based resin (j)”.
[0341] <Preparation of cross-linking agent solution>
[0342] Next, a crosslinking agent (C8) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 14.88 / 85.12 was diluted and stirred with toluene to prepare a crosslinking agent (C8) solution (solid content concentration 20 mass %). The SiH group content of the crosslinking agent (C8) was 5.0×10 -3 mol / g.
[0343] <Preparation of adhesive solution>
[0344] Next, 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S14) solution were mixed with 3.10 parts by mass (0.62 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 3.3) of a crosslinking agent (C8) solution and 1.20 parts by mass (0.48 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution "NYPER" manufactured by NOF Corporation [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stir and mix evenly. Next, use a disperser to prepare a solution having a solid content concentration of 15% by weight by diluting 4.27 parts by weight (0.64 parts by weight as solid content) of a photosensitive platinum (Pt) catalyst "trimethyl (methylcyclopentadienyl) platinum (IV)" manufactured by Sigma-Aldrich Japan Co., Ltd. with toluene, and stir and mix evenly to prepare a coating adhesive solution.
[0345] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 58 μm after drying was obtained.
[0346] (Comparative Example 5)
[0347] <Preparation of silicone resin solution>
[0348] The silicone resin (S15) prepared by mixing the silicone resin (b), the silicone resin (e), the silicone resin (h) and the silicone resin (j) in a mass ratio of (b) / (e) / (h) / (j) of 47.29 / 0.69 / 47.29 / 4.73 was diluted and stirred with toluene to prepare a silicone resin (S15) solution (solid content concentration 30% by mass). The mixing ratio ((G) / (R)) of the silicone rubber material (G) and the silicone resin (R) in the silicone resin (S15) was 36.2 / 63.8, and the alkenyl content was 2.3×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G) of the organic silicone resin (b)". alk )”, “organic silicone resin (e) organic silicone material (Galk )" and "organic silicone resin (h) organic silicone material (G 0 )”. In addition, the total mass of the silicone resin (R) is the total amount of “the silicone resin (R) of the silicone-based resin (b)”, “the silicone resin (R) of the silicone-based resin (h)” and “the silicone resin (R) of the silicone-based resin (j)”.
[0349] <Preparation of cross-linking agent solution>
[0350] Next, a crosslinking agent (C9) prepared by mixing a crosslinking agent (m) and a crosslinking agent (n) at a mass ratio (m) / (n) of 4.19 / 95.81 was diluted and stirred with toluene to prepare a crosslinking agent (C9) solution (solid content concentration 20% by mass). The SiH group content of the crosslinking agent (C9) was 3.1×10 -3 mol / g.
[0351] <Preparation of adhesive solution>
[0352] Next, 1.65 parts by mass (0.33 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 4.4) of a crosslinking agent (C9) solution and 2.38 parts by mass (0.95 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S15) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stirred and mixed uniformly. Then, 2.53 parts by mass (0.38 parts by mass in terms of solid content) of a solution of a platinum (Pt) metal catalyst "NC-25" (trade name, solid content concentration 25% by mass) manufactured by Dow Corning Toray Industries, Ltd. was added using a disperser, and stirred and mixed uniformly to prepare a coating adhesive solution.
[0353] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment area having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 30 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was bonded to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 68 μm after drying was obtained.
[0354] (Comparative Example 6)
[0355] <Preparation of silicone resin solution>
[0356] The silicone resin (S16) prepared by mixing the silicone resin (d), the silicone resin (e) and the silicone resin (i) in a mass ratio of (d) / (e) / (i) of 49.28 / 1.45 / 49.28 was diluted and stirred with toluene to prepare a silicone resin (S16) solution (solid content concentration 30% by mass). The silicone resin (S16) had a mixing ratio ((G) / (R)) of 65.5 / 34.5 for the silicone rubber material (G) and the silicone resin (R), and an olefin content of 4.6×10 -6 Here, the total mass of the organic silicone material (G) is "the organic silicone material (G of the organic silicone resin (d) alk )”, “organic silicone resin (e) organic silicone material (G alk )" and "organic silicone resin (i) organic silicone material (G 0 The total mass of the silicone resin (R) is the total mass of the “silicone resin (R) of the silicone-based resin (d)” and the “silicone resin (R) of the silicone-based resin (i)”.
[0357] <Preparation of cross-linking agent solution>
[0358] Next, in the same manner as in Example 10, a crosslinking agent (C6) solution (solid content concentration: 20% by mass) was prepared.
[0359] <Preparation of adhesive solution>
[0360] Next, 1.75 parts by mass (0.35 parts by mass in terms of solid content, SiH group / alkenyl molar ratio = 2.9) of a crosslinking agent (C6) solution and 2.48 parts by mass (0.99 parts by mass in terms of solid content, solid content concentration 40% by mass) of an organic peroxide solution [a mixture of di-(3-methylbenzoyl peroxide), benzoyl (3-methylbenzoyl) peroxide, and dibenzoyl peroxide] manufactured by NOF Corporation were mixed with 333.00 parts by mass (100 parts by mass in terms of solid content) of the silicone resin (S16) solution using a disperser. BMT-40K (trade name, 1 minute half-life temperature: 131.1°C)", and stirred and mixed uniformly. Then, 2.60 parts by mass (0.39 parts by mass in terms of solid content) of a solution of a platinum (Pt) metal catalyst "NC-25" (trade name, solid content concentration 25% by mass) manufactured by Dow Corning Toray Industries, Ltd. was added using a disperser, and stirred and mixed uniformly to prepare a coating adhesive solution.
[0361] Next, the adhesive solution was applied to a substrate 2 made of a polyethylene terephthalate (PET) film having a thickness of 38 μm. Then, the adhesive solution applied to the substrate 2 was initially dried in stages at a temperature of 40 to 90° C. in the front half of a drying furnace, and further dried for 3 minutes in a heat treatment zone having a maximum temperature of 160° C. in the rear half of the drying furnace, and the adhesive layer 3 was heated and cured to form an adhesive layer 3 having a thickness of 20 μm after drying. Next, a release liner subjected to a release treatment with a fluoroalkyl-modified silicone was attached to the adhesive layer 3. Thus, an adhesive tape 1 having a total thickness of 58 μm after drying was obtained.
[0362] Tables 1 to 3 show the layer configurations of the adhesive tapes 1 and the compositions of the adhesive layer 3 produced in Examples 1 to 10 and Comparative Examples 1 to 6.
[0363] [Table 1]
[0364]
[0365] [Table 2]
[0366]
[0367] [Table 3]
[0368]
[0369] 2. Evaluation Method
[0370] Next, the evaluation method of the adhesive tape 1 will be described.
[0371] (1) Adhesion test (before UV irradiation)
[0372] The adhesive tapes 1 prepared in Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to an adhesion test to BA-SUS (peel adhesion test) according to the method described in Adhesive Tape / Adhesive Sheet Test Methods (JIS Z 0237 (2009)).
[0373] Specifically, the adhesive tape 1 from which the release liner was peeled off was pasted on a stainless steel plate (SUS304) with a surface roughness (Ra) of 50±25 nm after bright annealing (BA), and a roller with a mass of 2000 g was reciprocated once at a speed of 5 mm / s for pressure bonding. Then, after leaving it for 20 to 40 minutes, it was peeled off at a speed of 5 mm / s in a direction 180° to the stainless steel plate using a tensile testing machine, and the adhesive force to the polished SUS plate was measured.
[0374] It should be noted that the adhesive tape 1 before irradiation with ultraviolet light (UV) is also subjected to an adhesion test. In addition, as a result of the adhesion test, if the fixing force when the adhesive tape 1 is used for cutting semiconductor materials is considered, it is preferably 2.4N / 10mm or more, and from the perspective of the pick-up property of the semiconductor chip or the like that is singulated by cutting, it is preferably 5.5N / 10mm or less. More preferably, it is 2.8N / 10mm or more and 5.5N / 10mm or less.
[0375] (2) Ball viscosity test
[0376] (2-1) Determination of initial (before UV irradiation) ball viscosity
[0377] The adhesive tapes 1 prepared in Examples 1 to 10 and Comparative Examples 1 to 6 before UV irradiation were subjected to a ball tack test in accordance with the method described in the adhesive tape and adhesive sheet test method (JIS Z 0237 (2009)).
[0378] (2-2) Determination of ball viscosity after UV irradiation
[0379] The adhesive tapes 1 prepared in Examples 1 to 10 and Comparative Examples 1 to 6 were irradiated with UV from the substrate side and left at a temperature of 23° C. and a humidity of 50±5% RH for 20 to 40 minutes. The release liner of each adhesive tape 1 was peeled off and a ball tack test was performed in the same manner as the initial (before UV irradiation) ball tack test according to the method described in the adhesive tape and adhesive sheet test method (JIS Z 0237 (2009)).
[0380] Regarding UV irradiation, a high-pressure mercury lamp was used, and the UV with a wavelength of 365 nm was adjusted so that the cumulative light intensity was 1200 mJ / cm 2 It should be noted that the accumulated light intensity was set to 3000 mJ / cm 2 The ball viscosity was also measured in the same manner, but no difference was observed when the cumulative light intensity was set to 1200 mJ / cm 2 Therefore, the accumulated light intensity is set to 1200mJ / cm 2 Make an evaluation.
[0381] As a result of the ball tack test, if the pick-up properties of semiconductor chips or the like separated by dicing are taken into consideration, it is preferred that the ball tack (ball number) after UV irradiation is lower than the initial (before UV irradiation) ball tack (ball number). That is, when the value of the ball number before UV irradiation is set to BN0 and the value of the ball number after UV irradiation is set to BN1, the relationship of BN0>BN1 is preferred. This relationship means that the second stage cross-linking reaction of the adhesive layer 3 can be promoted by UV irradiation, and the cohesive force is increased compared to before UV irradiation.
[0382] (3) Holding force test
[0383] (3-1) Determination of initial (before UV irradiation) retention
[0384] The adhesive tapes 1 before UV irradiation prepared in Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to a holding power test in accordance with the method described in the adhesive tape and adhesive sheet test method (JIS Z 0237 (2009)).
[0385] Specifically, the release liner of each adhesive tape 1 is peeled off, and the adhesive layer 3 is pasted on a stainless steel plate (SUS304) polished with water-resistant abrasive paper. In a state where a predetermined weight is installed, it is maintained at a temperature of 40°C and a humidity of 33% RH, and the time elapsed from the adhesive tape 1 being peeled off from the stainless steel plate to falling (falling time (minutes)) is measured. Furthermore, the failure mode of the adhesive tape 1 when it is peeled off from the stainless steel plate is observed (whether the failure mode between the adhesive layer 3 and the stainless steel plate is interface peeling or cohesive failure). It should be noted that the measurement of the falling time in the holding power test is carried out until 2880 minutes. In addition, as the results of the holding power test shown in Tables 4 to 6 described later, the falling time (minutes) and the failure mode of the adhesive tape 1 are shown.
[0386] (3-2) Determination of retention strength after UV irradiation
[0387] The adhesive tape 1 was irradiated with UV in the same manner as described in the measurement of ball tack after UV irradiation, and after leaving it to stand, a holding force test was performed in the same manner as the initial holding force test.
[0388] (3-3) Relationship between holding force and failure mode
[0389] Here, the relationship between the holding force of the adhesive tape 1 and the failure mode will be described. Figure 3 It is a schematic diagram showing the relationship between the crosslinking density of the silicone-based resin in the adhesive layer 3 and the result (drop time) of the holding force test of the adhesive tape 1 .
[0390] like Figure 3 As shown, in the adhesive tape 1, as the crosslinking density of the silicone resin in the adhesive layer 3 increases, the failure mode of the adhesive tape 1 relative to the stainless steel plate in the holding power test changes from [cohesive failure of the adhesive layer 3 (falling)] → [holding (not falling)] → [interface peeling (falling) between the adhesive layer 3 and the stainless steel plate].
[0391] In addition, if Figure 3 As shown, in the region where the failure mode of the adhesive tape 1 is cohesive failure, the holding force (drop time) of the adhesive tape 1 increases as the crosslinking density of the silicone-based resin in the adhesive layer 3 increases.
[0392] On the other hand, Figure 3 As shown in the figure, in the region where the failure mode of the adhesive tape 1 is interfacial peeling, the holding force (falling time) of the adhesive tape 1 decreases as the crosslinking density of the silicone resin in the adhesive layer 3 increases. This is presumably because as the crosslinking density of the silicone resin increases, the cohesive force of the adhesive layer 3 increases, and the adhesive force of the adhesive tape 1 decreases, resulting in the adhesive tape being easily peeled off from the stainless steel plate and falling off.
[0393] As a result of the holding force test, it is preferred that at least the failure mode after UV irradiation is holding or interface peeling, more preferably at least the failure mode after UV irradiation is interface peeling, and further preferably the failure modes at the initial stage (before UV irradiation) and after UV irradiation are both interface peeling. In addition, in the case where the failure modes at the initial stage (before UV irradiation) and after UV irradiation are both interface peeling, regarding the falling time, at the initial stage (before UV irradiation), from the perspective of the fixing force when the adhesive tape 1 is used for cutting of semiconductor materials, it is preferably as long as possible or not falling, and after UV irradiation, from the perspective of the pick-up of semiconductor chips, etc., which are singulated by cutting, it is preferably shorter than the initial stage (before UV irradiation).
[0394] In this case, when the adhesive tape 1 is used for dicing a semiconductor device substrate and the obtained semiconductor chips are peeled from the adhesive tape 1, UV irradiation on the adhesive tape 1 makes it difficult for adhesive residue to be generated on the semiconductor chips.
[0395] (4) Test on residual silicone resin
[0396] The adhesive tapes 1 prepared in Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to a residual adhesive test on the silicone resin.
[0397] First, agent A and agent B of a methyl-containing silicone resin (KER-2500N (trade name) manufactured by Shin-Etsu Chemical Co., Ltd.) as a silicone resin for LED devices were mixed at a mixing ratio of 1:1 to prepare a mixed solution. The mixed solution was applied to a stainless steel plate and heated at 100°C for 1 hour and further at 150°C for 2 hours to cure, thereby preparing a silicone test piece A.
[0398] Similarly, agent A and agent B of a phenyl-containing silicone resin (KER-6110 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd.) as a silicone resin for LED devices were mixed at a mixing ratio of 3:7 to prepare a mixed solution. The mixed solution was applied to a stainless steel plate and heated at 100°C for 2 hours and further at 150°C for 5 hours to cure, thereby preparing a silicone test piece B.
[0399] Next, the release liner of the adhesive tape 1 was peeled off, and the adhesive layer 3 was attached to the silicone test pieces A and B respectively, and a roller with a mass of 2000 g was reciprocated once at a speed of 5 mm / s for crimping. Next, the same conditions as those described in the measurement of ball adhesion after UV irradiation were operated, and UV was irradiated from the substrate 2 side of the adhesive tape 1, and then placed in an environment of temperature 40°C and humidity 90% RH for 120 hours. Then, at room temperature, the adhesive tape 1 was peeled off at a speed of 800 mm / s to 1200 mm / s in a direction of 90° to the silicone test pieces A and B, and the residual adhesive on the silicone test pieces A and B was confirmed by visual inspection.
[0400] (5) Test on epoxy resin residual glue
[0401] The adhesive tapes 1 prepared in Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to a residual adhesive test on epoxy resin.
[0402] For an epoxy test piece consisting of an epoxy resin plate (NL-EG-23 (trade name) manufactured by Nikko Chemical Co., Ltd.) obtained by impregnating epoxy resin in a glass cloth substrate, the adhesive layer 3 of the adhesive tape 1 with the release liner peeled off was pasted and crimped by reciprocating a roller with a mass of 2000 g once at a speed of 5 mm / s. Then, the adhesive tape 1 was irradiated with UV from the substrate 2 side in the same manner as the conditions described in the measurement of ball adhesion after UV irradiation, and then placed in an environment of temperature 40°C and humidity 90% RH for 120 hours. Then, at room temperature, the adhesive tape 1 was peeled off at a speed of 800 mm / s to 1200 mm / s in a direction of 90° to the epoxy test piece, and the residual adhesive on the epoxy test piece was confirmed by visual inspection.
[0403] The silicone resin residual adhesive test and the epoxy resin residual adhesive test were evaluated according to the following criteria: An evaluation of A or B was considered acceptable.
[0404] A: No residual adhesive within 100% of the test piece per unit area
[0405] B: Residual adhesive is observed within a range of less than 2% per unit area of the test piece
[0406] C: Residual adhesive is observed in the range of 2% or more and less than 5% per unit area of the test piece
[0407] D: Glue residue is observed in an area of 5% or more per unit area of the test piece, or glue residue is observed at the edge of the test piece.
[0408] (6) Cutting test
[0409] A cutting test was performed on the adhesive tapes 1 produced in Examples 1 to 10 and Comparative Examples 1 to 6.
[0410] Specifically, first, a molding epoxy resin (CEL-400ZHF40-W75G (trade name) manufactured by Hitachi Chemical Co., Ltd.) was charged into a mold and sealed at a pressure of 50 kgf / cm 2 (491N / cm 2 ), the sealing material was heat cured under the conditions of a thickness of 0.3 mm and a heating temperature of 150° C.×300 seconds to produce a circular plate-shaped (diameter 200 mm (8 inches)) cut test piece.
[0411] Next, the adhesive layer 3 of the adhesive tape 1 from which the release liner was peeled off was pasted on the cutting ring, and the portion that oozed out of the ring was cut off, and then further pasted on a fluorine-based release film (SS1A (trade name) manufactured by NIPPA Co., Ltd., thickness 75 μm). Next, a roller with a mass of 2000 g was reciprocated to press the adhesive tape 1 and the ring portion. Next, the fluorine-based release film was peeled off, and the cut test piece was pasted on the adhesive layer 3 in the center of the ring and pressed.
[0412] Furthermore, the dicing test piece was cut into 10 mm × 10 mm chips together with the adhesive tape 1 using a dicing device (A-WD-100A (trade name)) manufactured by Tokyo Seimitsu Co., Ltd. and a dicing blade manufactured by Disco Co., Ltd. At this time, the number of scattered chips was measured to evaluate the fixing force in the dicing test.
[0413] Next, the adhesive tape 1 attached to the singulated chips of 10 mm × 10 mm was irradiated with UV in the same conditions as described in the measurement of ball tack after UV irradiation. Then, the singulated chips were picked up from the adhesive tape 1, and the presence of residual adhesive on the chips was visually confirmed to evaluate the residual adhesive in the dicing test. In addition, the number of chips that failed to be picked up was measured to evaluate the pick-up performance in the dicing test.
[0414] The fixing force in the cutting test was evaluated according to the following criteria: An evaluation of A or B was considered acceptable.
[0415] A: The number of scattered chips is 0 out of 100, and no chip fragments are observed.
[0416] B: The number of scattered chips is 1 in 100, and no chip fragments are observed
[0417] C: The number of scattered chips is 2 out of 100, and no chip fragments are observed
[0418] D: The number of scattered chips is 3 or more in 100, or chip fragments are observed
[0419] The residual adhesive in the cutting test was evaluated according to the following criteria. An evaluation of A was considered acceptable.
[0420] A: No residual glue was observed on the chip
[0421] D: Residual adhesive is observed on the chip, or adhesive wire drawing is observed on the side of the chip
[0422] The pick-up property in the cutting test was evaluated according to the following criteria: An evaluation of A or B was considered acceptable.
[0423] A: The number of chips that failed to be picked up is 0 out of 100.
[0424] B: The number of chips that failed to be picked up is 1 in 100
[0425] C: The number of chips that failed to be picked up is 2 out of 100
[0426] D: The number of chips that failed to be picked up is more than 3 out of 100
[0427] 3. Test results
[0428] Tables 4 to 6 show the evaluation results of the adhesive tapes 1 of Examples 1 to 10 and Comparative Examples 1 to 6.
[0429] [Table 4]
[0430]
[0431] [Table 5]
[0432]
[0433] [Table 6]
[0434]
[0435] As shown in Tables 4 and 5, it was confirmed that in the adhesive tape 1 of Examples 1 to 10 in which the adhesive layer met the necessary conditions of the present invention, satisfactory results were obtained in the adhesion test, ball adhesion test, holding power test, silicone resin residual adhesive test, epoxy resin residual adhesive test, and cutting test (fixing force, residual adhesive and pickup properties).
[0436] This confirmed that the adhesive tapes 1 of Examples 1 to 10 are useful as adhesive tapes for dicing semiconductor materials, more specifically, as adhesive tapes for dicing that are attached from the sealing resin side of a semiconductor element substrate and used for dicing.
[0437] The content of alkenyl groups bonded to silicon atoms in the entire silicone resin is 2.9×10 -6mol / g or more and 4.1×10 -6 The adhesive tapes 1 of Examples 5, 7 and 10 within the range of mol / g or less were evaluated as good in all test items compared with the adhesive tapes 1 of other Examples. It should be noted that the mixing ratio ((G) / (R)) of the organic silicone material (G) and the organic silicone resin (R) of Examples 5, 7 and 10 was in the range of 41.5 / 58.5 to 50.4 / 49.6.
[0438] In contrast, as shown in Table 6, it was confirmed that the adhesive tapes 1 of Comparative Examples 1 to 6, in which the adhesive layer 3 did not satisfy the necessary conditions of the present invention, had all test results that were worse than those of Examples 1 to 10 in the silicone resin residual adhesive test, the epoxy resin residual adhesive test, and the cutting test (fixing force, residual adhesive, and pickup properties).
[0439] Specifically, in the adhesive tape 1 of Comparative Example 1 in which the adhesive layer 3 does not contain a crosslinking agent and a thermal polymerization initiator, a crosslinking reaction of the silicone resin does not occur even when heating or UV irradiation is performed, so no change in the results of the ball adhesion test and the holding force test is observed before and after UV irradiation, and the cohesive force is insufficient. Therefore, in the silicone resin residual glue test and the epoxy resin residual glue test for confirming practicality, a large amount of residual glue is observed. In addition, in the cutting test, since the cohesive force after UV irradiation as described above is not observed to increase, the chip pickup of the cutting test piece is poor, and residual glue is observed on the chip.
[0440] In the adhesive tape 1 of Comparative Example 2 in which the adhesive layer 3 does not contain a photosensitive platinum (Pt) catalyst but contains a conventional platinum (Pt) catalyst, the initial cohesion before UV irradiation increases, but even if UV irradiation is performed, the cohesion does not increase, and no change is observed in the results of the ball adhesion test and the holding force test before and after UV irradiation. Therefore, a large amount of residual adhesive is observed in the test of silicone resin residual adhesive and the test of epoxy resin residual adhesive. In addition, in the cutting test, the chip pickup of the cutting test piece is slightly poor, and a slightly large amount of residual adhesive is observed on the chip.
[0441] Furthermore, in the adhesive tape 1 of Comparative Example 3, in which the content of alkenyl groups bonded to silicon atoms in the silicone resin in the adhesive layer 3 was less than the lower limit of the necessary condition of the present invention, no change was observed in the results of the ball adhesion test and the holding force test before and after UV irradiation, and the cohesive force increase effect of the adhesive layer 3 brought about by UV irradiation was insufficient. Therefore, a large amount of residual adhesive was observed in the silicone resin residual adhesive test and the epoxy resin residual adhesive test. In addition, in the cutting test, the chip pickup of the cut test piece was poor, and residual adhesive was observed on the chip.
[0442] Furthermore, in the adhesive tape 1 of Comparative Example 4, in which the content of alkenyl groups bonded to silicon atoms in the silicone resin in the adhesive layer 3 exceeds the upper limit of the necessary conditions of the present invention, in the cutting test, the fixing force of the cut test piece is low, and a large number of chips are observed to fly during cutting. This is presumably because, in the stage before UV irradiation, that is, in the heating and drying process for forming the adhesive layer 3 on the substrate 2, the cross-linking reaction of the silicone rubber material (G) of the silicone resin in the adhesive layer 3 has been carried out by the thermal polymerization initiator, and it has been cured and become too hard. It should be noted that no residual glue was observed in the silicone resin residual glue test and the epoxy resin residual glue test. In addition, in the cutting test, no residual glue was observed for the chips that did not fly.
[0443] Furthermore, in the adhesive tape 1 of Comparative Example 5 in which the mixing ratio ((G) / (R)) of the organic silicone material (G) to the organic silicone resin (R) is less than the lower limit of the necessary condition of the present invention, since there is a large amount of organic silicone resin (R) that does not contribute substantially to the crosslinking of the adhesive layer 3, the effect of increasing the cohesive force of the adhesive layer 3 by UV irradiation is insufficient. Therefore, in the organic silicone resin residual adhesive test and the epoxy resin residual adhesive test, slightly more residual adhesive was observed. In addition, in the cutting test, the chip pickup of the cut test piece was slightly poor, and slightly more residual adhesive was observed on the chip.
[0444] Furthermore, in the adhesive tape 1 of Comparative Example 6, in which the mixing ratio ((G) / (R)) of the silicone material (G) and the silicone resin (R) in the silicone resin in the adhesive layer 3 exceeded the upper limit value of the necessary conditions of the present invention, in the cutting test, the fixing force of the cut test piece was low, and a large number of chips were observed to fly during cutting. This is presumably because, in the stage before UV irradiation, that is, in the heating and drying process for forming the adhesive layer 3 on the substrate 2, the cross-linking reaction of the silicone material (G) of the silicone resin in the adhesive layer 3 has been carried out by the thermal polymerization initiator, and it has been cured and become too hard. It should be noted that no residual glue was observed in the silicone resin residual glue test and the epoxy resin residual glue test. In addition, in the cutting test, no residual glue was observed for the chips that did not fly.
[0445] Explanation of symbols
[0446] 1: Adhesive tape, 2: Base material, 3: Adhesive layer, 100: Semiconductor element substrate, 101: Substrate, 102: Semiconductor element, 103: Sealing resin, 200: Semiconductor chip.
Claims
1. An adhesive tape for cutting, characterized in that: The adhesive layer comprises a substrate and an adhesive layer laminated on the substrate, and is used when dividing a semiconductor material having a plurality of semiconductor elements covered with a covering material into a plurality of semiconductor chips. The adhesive layer is composed of an adhesive composition, The adhesive composition comprises: an organic silicone resin obtained by mixing an organic silicone material (G) and an organic silicone resin (R), an organic polysiloxane having at least two hydrogen atoms bonded to silicon atoms, i.e., SiH groups, in one molecule as a crosslinking agent for the organic silicone resin, a peroxide as a thermal polymerization initiator, and a photosensitive platinum (Pt) catalyst. The mixing ratio (G) / (R) of the silicone rubber material (G) and the silicone resin (R) in the entire silicone-based resin is in the range of 40.0 / 60.0 to 56.0 / 44.0 in terms of mass ratio, The organic silicone material (G) comprises an organic silicone material (G) composed of an organopolysiloxane containing an alkenyl group bonded to a silicon atom. alk ), The content of the alkenyl groups bonded to the silicon atoms in the whole silicone resin is 7.0×10 -7 mol / g or more and 5.5×10 -6 The range is below mol / g.
2. The dicing adhesive tape according to claim 1, characterized in that: The semiconductor material in which the plurality of semiconductor elements are sealed with the covering material made of silicone resin is bonded from the covering material side for use.
3. The dicing adhesive tape according to claim 1 or 2, characterized in that: In the adhesive layer, the molar ratio of the total content of hydrogen atoms bonded to silicon atoms, i.e., SiH groups, of the cross-linking agent contained in the adhesive composition to the total content of alkenyl groups bonded to silicon atoms in the entire silicone-based resin contained in the adhesive composition, i.e., SiH groups / alkenyl groups bonded to silicon atoms, is in the range of greater than 2.0 and less than 10.
0.
4. The adhesive tape for dicing according to claim 1 or 2, characterized in that: In the adhesive layer, the content of the peroxide in the adhesive composition is in a range of 0.10 parts by mass or more and 3.00 parts by mass or less in terms of solid content relative to 100 parts by mass of the entire solid content of the silicone-based resin.
5. The dicing adhesive tape according to claim 1 or 2, characterized in that: In the adhesive layer, the peroxide is a diacyl peroxide.
6. The dicing adhesive tape according to claim 1 or 2, characterized in that: In the adhesive layer, the content of the photosensitive platinum (Pt) catalyst in the adhesive composition is in a range of 0.10 parts by mass or more and 3.00 parts by mass or less in terms of solid content relative to 100 parts by mass of the entire solid content of the silicone-based resin.
7. The adhesive tape for dicing according to claim 1 or 2, characterized in that: In the adhesive layer, the content of the alkenyl group bonded to the silicon atom in the entire silicone resin is 2.9×10 -6 mol / g or more and 4.1×10 - 6 The range is below mol / g.
8. The dicing adhesive tape according to claim 1 or 2, characterized in that: The adhesive properties according to JIS Z 0237 (2009) satisfy all of the following conditions (a) to (c): (a) the adhesive force to the BA-SUS test plate before light irradiation is in the range of 2.8 N / 10 mm or more and 5.5 N / 10 mm or less, (b) Regarding the ball number value in the inclined ball viscosity test at an inclination angle of 30°, a temperature of 23°C, and a relative humidity of 50% RH, when the ball number value before light irradiation is set to BN0 and the ball number value after light irradiation is set to BN1, the relationship of BN0>BN1 is established. (c) In the holding strength test after light irradiation at a temperature of 40°C, a relative humidity of 33% RH, and a standing time of 2880 minutes, the failure phenomenon when dropped means that the interface between the adhesive layer and the BA-SUS test plate is peeled off, or the adhesive layer does not drop in the holding strength test.
9. A method for manufacturing a semiconductor chip, comprising the following steps: A pasting step of pasting the dicing adhesive tape according to any one of claims 1 to 8 from the side of the sealing resin to a semiconductor element substrate having a plurality of semiconductor elements sealed with a sealing resin composed of a silicone resin formed on the substrate; A cutting step of cutting the semiconductor element substrate to which the dicing tape is attached into a plurality of semiconductor chips; an irradiation step of irradiating light to the dicing adhesive tape of the semiconductor element substrate; as well as The peeling step is to peel the dicing adhesive tape from the plurality of semiconductor chips.
Citation Information
Patent Citations
Dicing method
JP2005093503A
Adhesive tape for molding plastic lens and method for molding plastic lens
JP2012107125A
Adhesive tape for fixing semiconductor wafer, method for manufacturing semiconductor chip and adhesive tape with adhesive film
JP2013038408A
Adhesive tape for dicing and method of manufacturing semiconductor chip
JP2015050216A
Adhesive tape for dicing and method of manufacturing semiconductor chip
JP2016122812A